Heterophasic Polypropylene Copolymer

By using asymmetric hafnium bridged bisindenyl metallocene catalysts, a heterophase polypropylene copolymer with high molecular weight soluble part and high melting point crystalline part was prepared, which solved the problems of limited molecular weight capacity and low melting point in the prior art, and achieved the production of high-performance polymers.

CN114761450BActive Publication Date: 2025-03-28BOREALIS AG
View PDF 26 Cites 0 Cited by

Patent Information

Application Number
CN202080082488.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-11-26
Filing Date
2020-09-25
Publication Date
2025-03-28
Estimated Expiration
2040-09-25

AI Technical Summary

Technical Problem

When existing heterophase polypropylene copolymers are produced with ethylene-propylene copolymers in the gas phase, their molecular weight capabilities are limited and their melting point is low, which affects the stiffness and performance of the material.

Method used

Using asymmetric hafnium-bridged bisindenyl metallocene catalysts, a heterophase polypropylene copolymer with high molecular weight soluble moiety and high melting point crystalline moiety is prepared by adjusting the structure and combination of the catalysts.

Benefits of technology

The high tensile and impact properties of heterophase polypropylene copolymer are achieved, the stiffness and low temperature properties of the material are improved, and the melting point is between 156 and 164°C, meeting the needs of high-performance polymers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003662666600000021
    Figure BDA0003662666600000021
  • Figure BDA0003662666600000041
    Figure BDA0003662666600000041
  • Figure BDA0003662666600000131
    Figure BDA0003662666600000131
Patent Text Reader

Abstract

A heterophasic polypropylene copolymer having an MFR2 of 0.05 to 20 g / 10 min (determined according to ISO 1133 at 230°C with a load of 2.16 kg) and a melting point (Tm) of 156 to 164°C (measured by DSC according to ISO 11357), wherein the heterophasic polypropylene copolymer comprises at least the following components: (A) 55.0 to 95.0 wt% of a crystalline fraction (CF) having a comonomer content of 0 to 3.0 wt%; (B) 5.0 to 45.0 wt% of a soluble fraction (SF) having a comonomer content of 12 to 45 wt%; wherein the intrinsic viscosity (IV) of the soluble fraction (SF) (in decalin at 135°C) is from 2.5 to 11 dl / g, wherein the amount of the crystalline fraction (CF) and the amount of the soluble fraction (SF) are determined in 1,2,4-trichlorobenzene at 40°C.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to heterophasic polypropylene copolymers which can be prepared by certain bis-indenyl metallocene catalysts. In particular, the heterophasic polypropylene copolymers of the present invention have a high molecular weight soluble fraction (B), thus having a low MFR, and a high melting point crystalline fraction (A). Background Art

[0002] Metallocene catalysts have been used for many years to produce polyolefins. Numerous academic and patent publications describe the use of these catalysts in the polymerization of olefins. Metallocenes are now used in industry, especially polyethylene and polypropylene are usually produced using cyclopentadienyl-based catalyst systems with different substitutions.

[0003] These metallocenes are commonly used to prepare polypropylene, such as isotactic polypropylene. The structure of metallocenes has been optimized to produce high molecular weight isotactic polypropylene, but when producing heterophasic polypropylene with ethylene-propylene copolymers in the gas phase, its molecular weight capacity is usually limited. It is known that for a given rubber comonomer composition, the tensile and impact properties of heterophasic polypropylene can be improved by increasing the molecular weight of the rubber phase (for example, as described in J.Appl.Polym.Sci.2002,vol.85,pp.2412-2418 and J.Appl.Polym.Sci.2003,vol.87,pp.1702-1712). However, typically, the molecular weight of ethylene-propylene rubber is less than 4dl / g (measured as intrinsic viscosity IV (EPR), measured in decalin at 135°C.

[0004] In addition, metallocene catalysts that can be used to prepare heterophasic polypropylene tend to produce homopolymer matrices (and therefore heterophasic polypropylene polymers as a whole) with relatively low melting points (Tm), typically below 155 to 157°C. It is well known that higher Tm values ​​are beneficial to the stiffness of the material. The combination of a high melting point of the homopolymer matrix (or a high melting point of the heterophasic polypropylene itself) and a high molecular weight in the EPR rubber component is particularly desirable.

[0005] In this respect, a heterophasic polypropylene is a polypropylene comprising a propylene homopolymer matrix (or a propylene copolymer matrix having a low comonomer content, ie a random propylene copolymer) and a propylene ethylene (or propylene-ethylene-1-butene) rubber component typically dispersed in the matrix.

[0006] The present inventors have found that heterophasic polypropylene copolymers having advantageous properties can be prepared using certain metallocene catalysts.

[0007] The metallocene complex used to prepare the heterophasic polypropylene copolymer of the present invention is an asymmetric hafnium-bridged bis-indenyl structure. Some metallocenes disclosed in the prior art are similar to the one used.

[0008] C2-symmetric metallocenes are disclosed in WO2007 / 116034. This document reports the synthesis and characterization of, inter alia, the metallocene racemic-Me2Si(2-Me-4-Ph-5-OMe-6-tBuInd)2ZrCl2, and the use of the metallocene as a polymerization catalyst for homopolymerization of propylene and copolymerization of propylene with ethylene and higher alpha-olefins in solution polymerization after activation with MAO. The IV values ​​of the obtained polymers are about 3 to 3.4 dl / g, measured in tetralin (THN) at 135°C. The IV values ​​measured in decalin are about 20% higher than those measured in THN.

[0009] WO2006 / 097497 describes, in particular, rac-Me2Si(2-methyl-4-phenyl-1,5,6,7-tetrahydro-s-indacen-1-yl)2ZrCl2 supported on silica and its use in the homopolymerization and copolymerization of propylene and ethylene. The resulting polymers have an IV value of about 3 to 3.4 dl / g, measured in THN at 135°C.

[0010] WO2006 / 100258 describes the preparation of heterophasic polypropylene using pseudo-racemic dimethylsilanediyl-(6-methyl-4-(4'-tert-butylphenyl)-1,2,3,5-tetrahydro-s-indacen-7-yl)(2-isopropyl-4-(4'-tert-butylphenyl)-1-indenyl)-zirconium dichloride, but likewise reports low IVs values.

[0011] EP2072546 describes the synthesis of heterophasic polypropylene using unsupported asymmetric metallocene dimethylsilyl[(2-methyl-(4'-tert-butyl)-4-phenyl-indenyl)(2-isopropyl-(4'-tert-butyl)-4-phenyl-indenyl)]zirconium dichloride. The highest IV of the EPRs measured in decalin at 135°C was reported to be 3.4 dl / g.

[0012] EP2072584 describes the synthesis of heterophasic polypropylene using unsupported asymmetric metallocene dimethylsilyl[(2-methyl-(4'-tert-butyl)-4-phenyl-indenyl)(2-isopropyl-(4'-tert-butyl)-4-phenyl-indenyl)]zirconium dichloride. The highest IV of the EPRs measured in decalin at 135°C is reported to be 2 dl / g.

[0013] The following table lists many known metallocene catalyst complexes:

[0014]

[0015] The IV (XS) value of the above metallocene structure is 3.4 dl / gdl / g, measured in decalin at 135°C.

[0016] WO2016 / 038210 and WO2016 / 038211 also describe heterophasic polypropylene polymerization using, for example, rac-dimethylsilylene-bis(6-tert-butyl-2-isobutyl-5-methoxy-4-phenyl-1H-inden-1-yl)zirconium dichloride. The IV(EPR) values ​​are low, for example 3.0 dl / gdl / g or less.

[0017] In EP 2 829 558, the use of borate co-activators in unsupported single site catalysts showed that the borate co-activators had an adverse effect on the molecular weight of the rubber.

[0018] In WO 2013 / 007650 various heterophasic polypropylene copolymers with a low IV (XS) and a high XS fraction are described.

[0019] In EP 2 824 142 heterophasic polypropylene copolymers with low IV (XS) and high MFR are prepared.

[0020] In EP 3 201 268 a heterophasic polypropylene copolymer is combined with a polypropylene homopolymer. The heterophasic polypropylene copolymer described is a copolymer with a large amorphous part and a low IV (XS).

[0021] WO2019 / 179959 describes catalysts suitable for preparing certain lower melting heterophasic polypropylene copolymers.

[0022] WO 2011 / 160946 discloses blends comprising heterophasic copolymers and propylene hexene copolymers.

[0023] EP-A-2368937 discloses heterophasic polypropylene copolymers having a broad molecular weight distribution and a high intrinsic viscosity prepared in a multi-step reaction.

[0024] The inventors sought heterophasic polypropylene polymers with higher tensile and impact properties and with good stiffness, especially at low temperatures. The solution to this problem is the subject matter claimed, wherein in particular the molecular weight of the soluble fraction is high and the melting point of the heterophasic polypropylene copolymer is high. We surprisingly found that these heterophasic polypropylene copolymers with high IV (SF) can also be prepared using certain metallocenes. Summary of the invention

[0025] Viewed from one aspect, the present invention provides a heterophasic polypropylene copolymer having an MFR2 of 0.05 to 20 g / 10 min (ISO 1133 at 230°C, 2.16 kg load) and a melting point (Tm) of 156 to 164°C (measured by DSC according to ISO 11357), wherein the heterophasic polypropylene copolymer comprises at least the following components:

[0026] (A) 55.0 to 95.0 wt. % of a crystalline fraction (CF) having a comonomer content of 0 to 3.0 wt. %; and

[0027] (B) 5.0 to 45.0 wt. % of a soluble fraction (SF) having a comonomer content of 12 to 45 wt. %;

[0028] wherein the intrinsic viscosity (IV) of the soluble fraction (SF) (in decalin at 135°C) is 2.5 to 11 dl / g, and

[0029] The amount of the crystalline fraction (CF) and the amount of the soluble fraction (SF) were determined in 1,2,4-trichlorobenzene at 40°C.

[0030] Viewed from another aspect the invention provides a heterophasic polypropylene copolymer as claimed in claim 1 having an MFR2 of 0.1 to 20 g / 10 min (ISO 1133 at 230°C with a load of 2.16 kg) and a melting point (Tm) of 157 to 164°C (measured by DSC according to ISO 11357), wherein the heterophasic polypropylene copolymer comprises at least the following components:

[0031] (A) 55.0 to 80.0 wt. % of a crystalline fraction (CF) having a comonomer content of 0 to 3.0 wt. %; and

[0032] (B) 20.0 to 45.0 wt. % of a soluble fraction (SF) having a comonomer content of 12 to 40 wt. %;

[0033] wherein the intrinsic viscosity (IV) of the crystalline portion (CF) (in decalin at 135°C) is from 1.5 to 5.0 dl / g; and

[0034] wherein the intrinsic viscosity (IV) of the soluble fraction (SF) (in decalin at 135°C) is 4.5 to 11 dl / g, and

[0035] The amount of the crystalline fraction (CF) and the amount of the soluble fraction (SF) were determined in 1,2,4-trichlorobenzene at 40°C.

[0036] Viewed from another aspect, the present invention provides a heterophasic polypropylene copolymer having an MFR2 of 0.05 to 2.5 g / 10 min (ISO 1133 at 230°C, 2.16 kg load) and a melting point (Tm) of 156 to 163°C,

[0037] The heterophasic polypropylene copolymer comprises at least the following components:

[0038] (A) 75.0 to 95.0 wt. % of a crystalline fraction (CF) having a comonomer content of 0 to 2.0 wt. %; and

[0039] (B) 5.0 to 25.0 wt. % of a soluble fraction (SF) having a comonomer content of 12 to 45 wt. %;

[0040] wherein the intrinsic viscosity (IV) of the soluble fraction (SF) (in decalin at 135°C) is 2.5 to 10 dl / g, and

[0041] The amount of the crystalline fraction (CF) and the amount of the soluble fraction (SF) were determined in 1,2,4-trichlorobenzene at 40°C.

[0042] Viewed from another aspect, the present invention provides a heterophasic polypropylene copolymer having an MFR2 of 0.05 to 2.5 g / 10 min and a melting point (Tm) of 156 to 163° C.,

[0043] The heterophasic polypropylene copolymer comprises at least the following components:

[0044] (A) 75.0 to 95.0 wt% of a crystalline fraction (CF) having 0 to 2.0 wt% of ethylene (C2); and

[0045] (B) 5.0 to 25.0 wt% of a soluble fraction (SF), wherein C2 (SF) is in the range of 12 to 40 wt% and the intrinsic viscosity (SF) is 2.5 to 10 dl / g.

[0046] In one embodiment, the heterophasic polypropylene copolymers of the present invention may be prepared using a metallocene complex of formula (I):

[0047]

[0048] Each X is a σ-ligand;

[0049] In the R2Si- group, at least one R is methyl or ethyl and the other R is selected from methyl, ethyl, n-propyl, isopropyl, n-butyl or isobutyl, pentyl, hexyl, cyclohexyl and phenyl;

[0050] Each R 1 are independently the same or may be different and are CH2-R 7 Group, where R 7 Is H or straight or branched chain C 1-6 Alkyl, C 3-8 Cycloalkyl or C 6-10 Aryl;

[0051] Each R 2 are independently -CH=, -CY=, -CH2-, -CHY- or -CY2- groups, wherein Y is C 1-6 Hydrocarbyl wherein n is 2-6;

[0052] Each R 3 and R 4 are independently the same or may be different and are hydrogen, straight chain or branched C 1-6 Alkyl, C 7-20 Aralkyl, C 7-20 Alkyl aryl, C 6-20 Aryl or -OY group, where Y is C 1-6 Hydrocarbon;

[0053] R 5 Straight or branched chain C 1-6 Alkyl, C 7-20 Aralkyl, C 7-20 Alkyl aryl or C 6-20 aryl; and

[0054] R 6 C(R 8 )3 groups, R 8 Straight or branched chain C 1-6 alkyl;

[0055] (A) wherein each phenyl group has at least one R 3 and at least one R 4 is not hydrogen, and wherein for each phenyl group at least one R 3 and at least one R 4 is hydrogen; or

[0056] (B) One of the R 3 is an -OY group, where Y is C 1-6 Hydrocarbon, at the 4-position of each phenyl group, two additional R 3 The group is tert-butyl; and / or

[0057] (C) One of the R 4 is an -OY group, where Y is C 1-6 Hydrocarbon, at the 4th position of the benzene ring, the other two R 4 The group is tert-butyl.

[0058] From another aspect, the heterophasic polypropylene copolymer of the present invention can be prepared using a metallocene catalyst comprising

[0059] (i) a metallocene catalyst complex of formula (I) as defined above; and

[0060] (ii) A promoter comprising a compound of a Group 13 element.

[0061] The catalyst suitable for preparing the heterophasic polypropylene copolymer of the present invention can be used in non-supported form or solid form. The catalyst can be used as a homogeneous catalyst or a heterogeneous catalyst. The catalyst in solid form, preferably in the form of solid particles, can be supported on an external support material, such as silicon dioxide or aluminum oxide or mixed oxides such as silicon dioxide-aluminum oxide, or in one embodiment, does not contain an external support, but is still in solid form, as described in WO2003 / 051934.

[0062] Catalysts suitable for preparing the heterophasic polypropylene copolymers of the present invention may include

[0063] (i) a metallocene complex of formula (I) as defined above;

[0064] (ii) a promoter comprising a compound of a Group 13 element; and

[0065] (iii) Silica support.

[0066] The catalyst suitable for preparing the heterophasic polypropylene copolymer of the present invention may also be a solid catalyst, which can be obtained by the following method:

[0067] (a) forming a liquid / liquid emulsion system comprising a solution of catalyst components (i) and (ii) dispersed in a solvent to form dispersed droplets; and

[0068] (b) Solid particles are formed by solidifying the dispersed droplets.

[0069] Viewed from another aspect the invention provides a process for the preparation of a heterophasic polypropylene copolymer as hereinbefore defined comprising polymerising:

[0070] (I) polymerizing propylene and optionally ethylene and / or 1-butene in the presence of a catalyst to form:

[0071] a1) a crystalline fraction (CF) comprising a propylene homopolymer or a propylene copolymer with ethylene and / or 1-butene with 0 to 3 wt.-% comonomer as said matrix component; and

[0072] (II) subsequently polymerizing additional propylene and ethylene and optionally 1-butene in the presence of the matrix component of step (I), preferably in the gas phase, to form:

[0073] a2) a propylene-ethylene copolymer or a propylene-ethylene-1-butene copolymer soluble fraction (SF) having a comonomer content of 12 to 45% by weight;

[0074] The crystalline part (CF) accounts for 55.0 to 95.0 wt. % of the heterophasic propylene-ethylene copolymer or the heterophasic propylene-ethylene-1-butene copolymer, the soluble part (SF) accounts for 5.0 to 45.0 wt. %,

[0075] wherein the amount of the crystalline fraction (CF) and the amount of the soluble fraction (SF) are determined in 1,2,4-trichlorobenzene at 40°C; and wherein

[0076] The soluble fraction (SF) of the heterophasic propylene-ethylene copolymer or the heterophasic propylene-ethylene-1-butene copolymer has an intrinsic viscosity IV (SF) in decalin at 135°C of 2.5 to 11 dl / g.

[0077] In particular, the method requires

[0078] (I) polymerizing propylene and optionally ethylene and / or 1-butene in the presence of a catalyst according to the invention to form:

[0079] a1) a crystalline fraction (CF) comprising a propylene homopolymer or a propylene copolymer wherein ethylene and / or 1-butene with up to 2 wt.-% comonomers as the matrix component; and

[0080] (II) subsequently polymerizing additional propylene and ethylene and optionally 1-butene in the presence of the matrix component of step (I), preferably in the gas phase, to form:

[0081] a2) a propylene-ethylene copolymer or a propylene-ethylene-1-butene copolymer soluble fraction (SF) having a comonomer content of 12 to 45% by weight;

[0082] The crystalline part (CF) accounts for 75.0 to 95.0 wt. % of the heterophasic propylene-ethylene copolymer or the heterophasic propylene-ethylene-1-butene copolymer, the soluble part (SF) accounts for 5.0 to 25.0 wt. %,

[0083] wherein the amount of the crystalline fraction (CF) and the amount of the soluble fraction (SF) are determined in 1,2,4-trichlorobenzene at 40°C; and wherein

[0084] The intrinsic viscosity IV (SF) of the soluble fraction (SF) of the heterophasic propylene-ethylene copolymer or the heterophasic propylene-ethylene-1-butene copolymer in decalin at 135°C is preferably from 2.5 to 10 dl / g, preferably from 4.5 to 9.0 dl / g, most preferably from 5.5 to 8.0 dl / g.

[0085] Preferably the comonomer is ethylene only.

[0086] definition

[0087] Throughout this description, the following definitions are used:

[0088] By "external support-free" is meant that the catalyst does not comprise an external support, such as an inorganic support, for example silica or alumina, or an organic polymeric support material.

[0089] The term "C 1-20 "Hydrocarbon" includes C 1-20 Alkyl, C 2-20 Alkenyl, C 2-20 Alkynyl, C 3-20 Cycloalkyl, C 3-20 Cycloalkenyl, C 6-20 Aryl, C 7-20 Alkyl aryl or C 7-20 Aralkyl or mixtures of these groups, such as cycloalkyl substituted by alkyl. Straight chain and branched hydrocarbon groups cannot contain cyclic units. Aliphatic hydrocarbon groups cannot contain aromatic rings.

[0090] Unless otherwise stated, the preferred C 1-20 The hydrocarbon group is C1 -20 Alkyl, C 4-20 Cycloalkyl, C 5-20 Cycloalkyl-alkyl, C 7-20 Alkyl aryl, C 7-20 Arylalkyl or C 6-20 Aryl, especially C 1-10 Alkyl, C 6-10 Aryl or C 7-12 Arylalkyl, such as C 1-8 The most particularly preferred hydrocarbon groups are methyl, ethyl, propyl, isopropyl, tert-butyl, isobutyl, C 5-6 - cycloalkyl, cyclohexylmethyl, phenyl or benzyl.

[0091] When complex definitions are involved, the term "halo" includes fluoro, chloro, bromo and iodo groups, especially chloro or fluoro groups.

[0092] The oxidation state of a metal ion is determined primarily by the nature of the metal ion in question and the stability of the individual oxidation state of each metal ion.

[0093] It will be appreciated that in the complexes of the present invention, the metal ion is coordinated by the ligand X to satisfy the valency of the metal ion and to fill its available coordination sites. The nature of these σ-ligands may vary widely.

[0094] The numbering of these rings is obvious from the structure of this article.

[0095] In this application, catalyst activity is defined as the amount of polymer produced per gram of catalyst per hour. In this application, catalyst metal activity is defined as the amount of polymer produced per gram of metal per hour. The term productivity is sometimes also used to refer to catalyst activity, although in this context it refers to the amount of polymer produced per unit weight of catalyst.

[0096] Unless otherwise indicated, the term "molecular weight" as used herein refers to the weight average molecular weight Mw.

[0097] The amount of crystalline fraction (CF) and the amount of soluble fraction (SF) are determined in 1,2,4-trichlorobenzene at 40°C. The crystalline fraction is the part of the heterophasic propylene copolymer which is insoluble in the solvent. The soluble fraction is correspondingly the dissolved part.

[0098] In the present invention, the term "matrix" should be interpreted according to its generally accepted meaning, that is, it refers to a continuous phase (a continuous polymer phase in the present invention) in which separate or discrete particles, such as rubber particles, may be dispersed. The propylene polymer is present in an amount such that it forms a continuous phase that can serve as a matrix.

[0099] Furthermore, the terms "amorphous copolymer", "dispersed phase", "predominantly amorphous copolymer" and "rubber phase" represent the same meaning and are interchangeable in the present invention. Amorphous means that when the copolymer is analyzed by DSC as a pure component (after extraction from the matrix by xylene extraction), its heat of fusion is less than 20 J / g.

[0100] The expression homopolymer as used in the present invention relates to a polypropylene which consists essentially of propylene units. In a preferred embodiment only the propylene units of the propylene homopolymer are detectable.

[0101] Detailed description of the invention

[0102] The present invention relates to heterophasic polypropylene copolymers that can be prepared using certain metallocene catalysts having a desirable combination of a high matrix melting point, a low soluble fraction content and a soluble fraction having a low ethylene content.

[0103] In some embodiments, the soluble portion (or rubber phase or amorphous portion) has a high molecular weight, eg, a high intrinsic viscosity. The crystalline portion (or matrix phase), and thus the heterophasic polypropylene copolymer itself, has a high melting point.

[0104] Heterophasic Polypropylene Copolymer

[0105] The heterophasic polypropylene copolymer of the present invention has an MFR2 of 0.05 to 20 g / 10 min (ISO 1133 at 230°C, load of 2.16 kg) and a melting point (Tm) of 156 to 164°C (measured by DSC according to ISO 11357), wherein the heterophasic polypropylene copolymer comprises at least the following components:

[0106] (A) 55.0 to 95.0 wt. % of a crystalline fraction (CF) having a comonomer content of 0 to 3.0 wt. %; and

[0107] (B) 5.0 to 45.0 wt. % of a soluble fraction (SF) having a comonomer content of 12 to 45 wt. %;

[0108] wherein the intrinsic viscosity (IV) of the soluble fraction (SF) (in decalin at 135°C) is 2.5 to 11 dl / g, and

[0109] The amount of the crystalline fraction (CF) and the amount of the soluble fraction (SF) were determined in 1,2,4-trichlorobenzene at 40°C.

[0110] In a preferred embodiment the heterophasic polypropylene copolymer of the present invention has an MFR2 of 0.1 to 20 g / 10 min (ISO 1133 at 230°C with a load of 2.16 kg) and a melting point (Tm) of 157 to 164°C (measured by DSC according to ISO 11357), wherein the heterophasic polypropylene copolymer comprises at least the following components:

[0111] (A) 55.0 to 80.0 wt. % of a crystalline fraction (CF) having a comonomer content of 0 to 3.0 wt. %; and

[0112] (B) 20.0 to 45.0 wt. % of a soluble fraction (SF) having a comonomer content of 12 to 40 wt. %;

[0113] wherein the intrinsic viscosity (IV) of the crystalline portion (CF) (in decalin at 135°C) is from 1.5 to 5.0 dl / g; and

[0114] wherein the intrinsic viscosity (IV) of the soluble fraction (SF) (in decalin at 135°C) is 4.5 to 11 dl / g, and

[0115] The amount of the crystalline fraction (CF) and the amount of the soluble fraction (SF) were determined in 1,2,4-trichlorobenzene at 40°C.

[0116] In a preferred embodiment the heterophasic polypropylene copolymer of the present invention has an MFR2 of 0.05 to 2.5 g / 10 min (according to ISO 1133 at 230°C, 2.16 kg load) and a melting point (Tm) of 156 to 163°C.

[0117] The heterophasic polypropylene copolymer comprises at least the following components:

[0118] (A) 75.0 to 95.0 wt. % of a crystalline fraction (CF) having a comonomer content of 0 to 2.0 wt. %; and

[0119] (B) 5.0 to 25.0 wt. % of a soluble fraction (SF) having a comonomer content of 12 to 45 wt. %;

[0120] wherein the intrinsic viscosity (IV) of the soluble fraction (SF) (in decalin at 135°C) is 2.5 to 10 dlL / g, and

[0121] The amount of the crystalline fraction (CF) and the amount of the soluble fraction (SF) were determined in 1,2,4-trichlorobenzene at 40°C.

[0122] The properties of the rubber component (i.e. the SF soluble fraction) can be adjusted to achieve surprisingly high molecular weights. Furthermore, we show that the heterophasic copolymers of the present invention have very high melting points (Tm) of 156 to 164°C, preferably 156 to 163°C, more preferably 156 to 162°C, such as 157 to 162°C, still more preferably 158 to 162°C.

[0123] The heterophasic propylene copolymers (HECOs) of the present invention effectively comprise a polymer matrix (M), which is a propylene homopolymer (hPP) or a random propylene-ethylene or propylene-ethylene-1-butene copolymer (rPP) or a combination of both, wherein a predominantly amorphous copolymer (B) is dispersed, like a propylene-ethylene copolymer (EP) (i.e. a rubber phase, like EPR).

[0124] Thus, the polypropylene matrix (M) comprises (finely) dispersed inclusions which are not part of the matrix and said inclusions comprise the amorphous copolymer (B). The matrix component (M) can be considered as the crystalline part (or insoluble part). The amorphous or rubber part can be considered as the soluble part (SF).

[0125] The term "heterophasic polypropylene copolymer" as used herein refers to a copolymer comprising a matrix part (polypropylene homopolymer or propylene copolymer) and dispersed in said matrix a predominantly amorphous copolymer (B) as defined in more detail below.

[0126] Matrix (M) / Crystalline fraction (CF)

[0127] The following embodiments apply equally to the matrix component / crystalline fraction.The crystalline fraction is the fraction of the heterophasic polypropylene copolymer which is insoluble in 1,2,4-trichlorobenzene at 40°C.

[0128] The matrix (M) / crystalline part of the heterophasic polypropylene copolymer is preferably a propylene homopolymer or a semicrystalline propylene-ethylene or propylene-butene copolymer or a propylene-ethylene butene copolymer or a combination thereof. The term "semicrystalline" means that the copolymer has a well defined melting point and a heat of fusion above 50 J / g.

[0129] The comonomer content in this component is low, i.e. 2.0 wt% or less, more preferably less than 1.0 wt% comonomer is present in the matrix component / crystalline portion, e.g. 0.5 wt% or less. Ideally, the matrix component / crystalline portion is a propylene homopolymer. If a comonomer is present, it is preferably ethylene.

[0130] In one embodiment the matrix (M)) / crystalline part comprises, preferably consists of, a propylene homopolymer as defined above or below.

[0131] The polypropylene homopolymer may comprise or consist of a single polypropylene homopolymer fraction (= unimodal) but may also comprise mixtures of different polypropylene homopolymer fractions.

[0132] The polypropylene homopolymer is understood to be bimodal or multimodal in case the polypropylene homopolymer comprises different fractions. These fractions may have different average molecular weights or different molecular weight distributions.

[0133] Preferably the polypropylene homopolymer may be bimodal or multimodal with respect to molecular weight or molecular weight distribution.

[0134] Alternatively, and preferably, the polypropylene homopolymer may be unimodal with respect to the average molecular weight and / or molecular weight distribution.

[0135] Thus, in one embodiment or the present invention the matrix (M)) / crystalline fraction is unimodal, whereas in another embodiment the matrix (M)) / crystalline fraction is bimodal and consists of the two propylene homopolymer fractions (hPP-1) and (hPP-2).

[0136] In another embodiment, the matrix (M)) / crystalline fraction is bimodal and consists of one homopolymer fraction and one semicrystalline copolymer fraction.

[0137] Ideally, the matrix component is an isotactic polypropylene matrix component. The matrix component may consist of a single propylene homopolymer, but may also include a mixture of different propylene homopolymers. However, ideally a single propylene homopolymer is present.

[0138] The matrix component may have a melting point (Tm) of 156 to 162°C, preferably 158 to 161°C.

[0139] The MFR2 of the matrix component / crystalline part (A) may be in the range of 0.01 to 15 g / 10min, for example 0.1 to 10 g / 10min, preferably 0.1 to 4.0 g / 10min.

[0140] In one embodiment 80.0 to 95.0 wt. % of component (A), preferably 85.0 to 95.0 wt. % of component (A) is present in the heterophasic polypropylene copolymer.

[0141] In a second embodiment, 65.0 to 85.0 wt. % of component (A) is present, preferably 70.0 to 80.0 wt. % of component (A) is present.

[0142] It is thus understood that the matrix (M) / crystalline portion can be considered as the component produced in the first stage of the polymerization process described in detail herein, or it can be considered as the component insoluble in 1,2,4-trichlorobenzene (1,2,4-TCB).

[0143] Thus, the amorphous portion (B) may be considered as a component produced in the second stage of the polymerization process described in detail herein, or it may be considered as a component soluble in 1,2,4-trichlorobenzene (1,2,4-TCB).

[0144] Amorphous Propylene Copolymer / Soluble Part:

[0145] The second component of the heterophasic polypropylene copolymer is the propylene copolymer fraction (B), which is preferably an amorphous copolymer of propylene and ethylene. The amorphous propylene copolymer may also be an amorphous propylene-ethylene-1-butene copolymer.

[0146] Thus, the second component is preferably an elastomeric copolymer, dispersed in said matrix (M) (ie the dispersed phase).

[0147] As stated above, the terms "amorphous (propylene-ethylene) copolymer", "dispersed phase" and "rubber phase" mean the same thing, i.e. are interchangeable for the purposes of the present invention.

[0148] The amorphous propylene-ethylene copolymer (B) is completely soluble in xylene at room temperature.

[0149] The amorphous propylene-ethylene copolymer (B) is completely soluble in 1,2,4-trichlorobenzene (1,2,4-TCB).

[0150] Like the propylene polymer matrix, the dispersed phase may be unimodal or multimodal, like bimodal.

[0151] In one embodiment, the dispersed phase is unimodal. More particularly, the dispersed phase is preferably unimodal with respect to intrinsic viscosity and / or comonomer distribution.

[0152] For the definition of unimodal and multimodal (eg bimodal), refer to the definitions above.

[0153] Preferably, the unimodal dispersed phase is produced in a single reaction stage, more preferably in a gas phase reactor, and comprises, for example consists of, one propylene-ethylene copolymer fraction.

[0154] In one embodiment, component (B) constitutes 5.0 to 25.0 wt %, preferably 5.0 to 20.0 wt %, more preferably 5.0 to 15.0 wt % of the polymer.

[0155] In a second embodiment, component (B) constitutes from 35.0 to 15.0 wt. %, preferably from 30.0 to 20.0 wt. % of the polymer.

[0156] The comonomer content, eg ethylene content, of the amorphous / soluble fraction may be from 12 to 40 wt%, preferably from 18 to 40 wt%, such as from 20 to 40 wt%.

[0157] The soluble portion is generally a random copolymer. It is preferably dispersed in the matrix, best achieved by producing an EPR phase in a multistage polymerization reaction after the matrix as defined below.

[0158] The MFR2 of the soluble part is preferably greater than 0.01 g / 10 min, preferably greater than 0.05 g / 10 min, more preferably greater than 0.1 g / 10 min, especially greater than 0.2 g / 10 min. The upper limit of the soluble part or MFR2 is preferably 10 g / 10 min.

[0159] If the MFR value of the component cannot be measured directly, it can be calculated from the intrinsic viscosity measurement according to the correlation defined in C. Grein, M. Gahleitner, B. Knogler and S. Nestelberger, Melt Viscosity Effects in Ethylene-Propylene Copolymers, Rheol. Acta, 46 (2007) 1083-1089. Based on the MFR of the total polymer and the MFR of the SF part, the MFR of the impact copolymer matrix component can be calculated using the logarithmic mixing rule, i.e., using the following equation

[0160] MFR (total) = 10 (1-w(SF))log10(MFR(基质))+w(SF)log10(MFR(SF))

[0161] Here, w(SF) is the weight fraction of the SF phase (B).

[0162] In all embodiments of the invention, the intrinsic viscosity of the soluble fraction IV (SF) is preferably at least 2.5 dl / g, such as at least 3.0 dl / g. The upper limit may be 11 dl / g, such as 10 dl / g. However, it is beneficial if IV (SF) is at least 3.5 dl / g, more preferably at least 4.0 dl / g, such as 4.5 to 10 dl / g, especially 5.0 to 9.0 dl / g, most especially 5.5 to 8.0 dl / g, wherein the intrinsic viscosity (SF) is measured in decalin at 135°C.

[0163] Final heterophasic propylene copolymer

[0164] As described below, the heterophasic propylene copolymer according to this invention may be prepared by sequential polymerization. Preferably, in at least one step a propylene homopolymer matrix is ​​prepared and in a subsequent step the amorphous propylene-ethylene copolymer (B) is prepared in the presence of the propylene homopolymer.

[0165] In order to characterize the matrix and the amorphous phase of heterophasic propylene copolymers several methods are known.

[0166] The crystalline fraction and the soluble fraction are separated by the CRYSTEX QC method using 1,2,4-trichlorobenzene (TCB) as solvent. The method is described in the measurement method section below. In this method, the crystalline fraction (CF) and the soluble fraction (SF) are separated from each other. The crystalline fraction (CF) corresponds mainly to the matrix phase, while the soluble fraction (SF) corresponds mainly to the elastomer phase.

[0167] It is preferred that the heterophasic propylene copolymer has a melting point (Tm) of 156 to 162 °C, preferably 157 to 161 °C, especially 158 to 161 °C.

[0168] It is preferred that the heterophasic propylene copolymer has an MFR2 of 0.1 to 2.5 g / 10 min, preferably 0.2 to 2.5 g / 10 min.

[0169] The final heterophasic polypropylene copolymer may have an MFR2 of 0.2 to 2.0 g / 10 min, such as 0.4 to 1.5 g / 10 min.

[0170] The final heterophasic polypropylene copolymer may have an MFR2 of 0.2 to 15 g / 10 min, such as 0.2 to 1.5.

[0171] Preferably, the heterophasic propylene copolymer has a xylene soluble fraction of 5.0 to 30 wt%.

[0172] In one embodiment it is preferred that the heterophasic propylene copolymer comprises 80.0 to 95.0 wt.-% of the crystalline fraction (CF).

[0173] In one embodiment it is preferred that the heterophasic propylene copolymer comprises 70.0 to 80.0 wt.-% of the crystalline fraction (CF).

[0174] In one embodiment it is preferred that the heterophasic propylene copolymer comprises 5.0 to 20.0 wt.-% of the soluble fraction (SF).

[0175] In one embodiment it is preferred that the heterophasic propylene copolymer comprises 30.0 to 20.0 wt.-% of the soluble fraction (SF).

[0176] Preferably the heterophasic propylene copolymer has a Mw / Mn of 1.0 to 4.0.

[0177] The final heterophasic polypropylene copolymer may have an IV measured in decalin at 135°C of 1.5 to 5.0 dl / g, such as 2.0 to 5.0 dl / g.

[0178] The final heterophasic polypropylene copolymer may have a flexural modulus of 800 MPa or more, preferably 800 to 1800 MPa, like 1200 to 1800 MPa (ISO 178).

[0179] The final heterophasic polypropylene copolymer may have a 2 , for example 42.0 to 70 kJ / m 2 Charpy notched impact strength (23°C).

[0180] The final heterophasic polypropylene copolymer may have a Charpy notched impact strength (-20°C) of at least 4.0 kJ / m2, preferably from 4.0 to 12 kJ / m2, such as from 4.0 to 7.0 kJ / m2.

[0181] The final heterophasic polypropylene copolymer may have a C2 content of 2.5 to 5.0 wt.-%, such as 3.0 to 4.0 wt.-%.

[0182] The 2,1-regio-error content in the heterophasic polypropylene copolymer may be from 0.01 to 0.6 mol%, preferably from 0.05 to 0.4 mol%.

[0183] Metallocene

[0184] The heterophasic polypropylene of the present invention can be prepared using metallocene catalysis. The metallocene complex in the catalyst can be asymmetric. Asymmetric means that the two ligands forming the metallocene are different.

[0185] The metallocene catalyst complex suitable for preparing the heterophasic polypropylene of the present invention is preferably a chiral racemic bridged bis-indenyl C1-symmetric metallocene in trans configuration.

[0186] Although the complexes of the present invention are formally C1-symmetric, the complexes ideally retain pseudo-C2-symmetry in that they retain C2-symmetry near the metal center, although not at the ligand periphery. In terms of their chemical properties, anti-enantiomer pairs and cis-enantiomer pairs (in the case of C1-symmetric complexes) are formed during the synthesis of the complexes. For the purposes of the present invention, racemic-trans means that the two indenyl ligands are oriented in opposite directions relative to the cyclopentadienyl-metal-cyclopentadienyl plane, while racemic-cis means that the two indenyl ligands are oriented in the same direction relative to the cyclopentadienyl-metal-cyclopentadienyl plane, as shown below

[0187]

[0188] Formula (I) and any subformulae are intended to encompass both cis and trans configurations.Preferred metallocene catalyst complexes are in the trans configuration.

[0189] The metallocene complex of the present invention is preferably used as the racemic trans isomer.Ideally, therefore at least 95 mol %, for example at least 98 mol %, in particular at least 99 mol % of the metallocene catalyst complex is in the racemic-trans isomer form.

[0190] Metallocene complexes

[0191] The metallocene complex of the present invention is represented by formula (I):

[0192]

[0193] In the complex of formula (I), each X is a sigma ligand. Most preferably, each X is independently a hydrogen atom, a halogen atom, a C 1-6 Alkoxy or R' group, wherein R' is C 1-6 Preferably, X is chloro, benzyl or methyl. Preferably, the two X groups are the same. The most preferred choice is two chloride ions, two methyl groups or two benzyl groups, especially two chloride ions.

[0194] In the bridging group R2Si-, at least one R is methyl or ethyl and the other R is selected from methyl, ethyl, n-propyl, isopropyl, n-butyl or isobutyl, pentyl, hexyl, cyclohexyl and phenyl.

[0195] Preferably, the formula R2Si- represents Me2Si-, Et2Si- or (cyclohexyl)Me-Si-. The most preferred bridge is -Si(CH3)2 or Et2Si-.

[0196] Each R 1 are independently the same or may be different and are CH2-R 7 Group, where R 7 Is H or straight or branched chain C 1-6 Alkyl, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl and tert-butyl, C 3-8 Cycloalkyl (e.g. cyclohexyl) or C 6-10 Aryl (preferably phenyl).

[0197] Preferably, the two R 1 The groups are the same and are CH2-R 7 Group, where R 7 Is H or straight or branched chain C 1-4 Alkyl, more preferably, two R 1 The groups are the same and are CH2-R 7 Group, where R 7H or straight or branched chain C 1-3 Most preferably, the two R 1 The groups are all methyl.

[0198] Each R 2 are independently -CH=, -CY=, -CH2-, -CHY- or -CY2- groups, wherein Y is C 1-10 Hydrocarbyl, preferably C 1-4 Hydrocarbyl wherein n is 2-6, preferably 3-4. Ideally, R 2 Together with the atoms of the benzene ring, they form a five-membered ring. 2 is -CH2- and n is 3.

[0199] Each substituent R 3 and R 4 are independently the same or may be different and are hydrogen, straight chain or branched C 1-6 Alkyl, C 7-20 Aralkyl, C 7-20 Alkyl aryl, C 6-20 Aryl or -OY group, where Y is C 1-6 Hydrocarbon. Requirements:

[0200] (A) Each phenyl group has at least one R 3 And at least one R 4 is not hydrogen, and wherein for each phenyl group at least one R 3 and at least one R 4 is hydrogen; or

[0201] (B) One R 3 is an -OY group, where Y is C 1-6 Hydrocarbon, at the 4-position of each phenyl group, two additional R 3 The group is tert-butyl; and / or

[0202] (C) One R 4 is an -OY group, where Y is C 1-6 Hydrocarbon, at the 4th position of the benzene ring, the other two R 4 The group is tert-butyl.

[0203] The benzene ring can be mono-, di- or tri-substituted.

[0204] More preferably, R 3 and R 4 is hydrogen or a straight or branched chain C 1-4 Alkyl or -OY group, where Y is C 1-4 Even more preferably, each R 3 and R 4are independently hydrogen, methyl, ethyl, isopropyl, tert-butyl or methoxy, especially hydrogen, methyl or tert-butyl, wherein at least one R 3 and at least one R 4 is not hydrogen and each phenyl group has at least one R 3 And at least one R 4 is hydrogen; or

[0205] At least one R 3 is a methoxy group, which is at the 4-position of each phenyl group, and the other two R 3 The group is tert-butyl; and / or

[0206] At least one R 4 is a methoxy group, which is at the 4th position of the benzene ring, and the other two R 4 It is tert-butyl.

[0207] Thus, in one embodiment, one or two R 3 Not hydrogen, but one or two R 3 The radical is hydrogen.

[0208] If each phenyl group has two non-hydrogen R 3 group, then R represents hydrogen 3 The group is preferably in the 4-position of the ring. If there are two R representing hydrogen 3 group, then non-hydrogen R 3 The group is preferably present in the 4-position of the ring.

[0209] Two R are preferred 3 The groups are the same. 3 The preferred structure of the two phenyl groups substituted by the group is 3',5'-dimethyl or 4'-tert-butyl. Alternatively, the structure is 3,5-di-tert-butyl-4-methoxyphenyl.

[0210] For the indenyl moiety, in one embodiment, one or both R 4 More preferably, the two R 4 The group is not hydrogen. If there are two non-hydrogen R 4 group, then R represents hydrogen 4 Preferably at position 4 of the ring. If there are two R representing hydrogen 4 Group, then non-hydrogen R 4 The group is preferably present in the 4-position of the ring.

[0211] Two R are preferred 4 The same, such as 3',5'-dimethyl or 3',5'-di-tert-butyl. Another option is 3',5'-di-tert-butyl-4-methoxyphenyl.

[0212] R 5 Is it a straight chain or branched chain C1-6 Alkyl, for example methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl and tert-butyl, C 7-20 Aralkyl, C 7-20 Alkyl aryl or C 6-20 Aryl.

[0213] R 5 Preferably, a straight chain or branched C 1-6 Alkyl or C 6-20 Aryl, more preferably straight chain C 1-4 Alkyl, even more preferably C1 or C2 alkyl, most preferably methyl.

[0214] R 6 C(R 8 )3 groups, R 8 Straight or branched chain C 1-6 alkyl;

[0215] Optimize each R 8 Same or different, R 8 Is it a straight chain or branched chain C 1-4 Alkyl, more preferably R 8 are the same and are C1 or C2 alkyl. Most preferably, all R 8 The groups are all methyl.

[0216] In a preferred embodiment, the present invention provides a metallocene complex represented by formula (II)

[0217]

[0218] Each X is selected from chlorine, benzyl and C 1-6 Alkyl σ-ligands;

[0219] R2Si- is Me2Si or Et2Si-;

[0220] Each R 3 and R 4 are independently the same or may be different and are hydrogen, straight chain or branched C 1-6 an alkyl group or an -OY group, wherein Y is C 1-6 Hydrocarbyl; wherein

[0221] (A) Each phenyl group has at least one R 3 and at least one R 4 is not hydrogen, and each phenyl group has at least one R 3 and at least one R 4 is hydrogen; or

[0222] (B) At least one R 3 is an -OY group, where Y is C 1-6 Hydrocarbon, at the 4th position of each benzene ring, the other two R3 The group is tert-butyl; and / or

[0223] (C) At least one R 4 is an -OY group, where Y is C 1-6 Hydrocarbon, at the 4th position of the benzene ring, the other two R 4 The group is tert-butyl;

[0224] R 5 Is it a straight chain or branched chain C 1-6 alkyl;

[0225] R 6 -C(R 8 )3 groups, R 8 It is a straight chain or branched C1 or C2 alkyl group.

[0226] More preferably, the metallocene complex of the present invention is one of the following:

[0227]

[0228] Each X is the same and is selected from chlorine, benzyl and C 1-6 Alkyl σ-ligands;

[0229] R2Si- is Me2Si or Et2Si-;

[0230] Each non-hydrogen R 3 Same, each non-hydrogen R 4 same;

[0231] R 3 is hydrogen, straight chain or branched chain C 1-6 alkyl;

[0232] R 4 is hydrogen, straight chain or branched chain C 1-6 alkyl;

[0233] Each phenyl group has at least one R 3 and at least one R 4 is not hydrogen, and wherein for each phenyl group at least one R 3 and at least one R 4 It is hydrogen;

[0234] R 5 Is it a straight chain or branched chain C 1-4 Alkyl; and

[0235] R 6 -C(R 8 )3 groups, R 8 It is a straight chain or branched C1 or C2 alkyl group.

[0236] In a further preferred embodiment, the present invention provides metallocene complexes represented by formula (IVa) to (IVd)

[0237]

[0238]

[0239] Where each X is the same and is chloro, benzyl or C 1-6 Alkyl, preferably chloro, benzyl or methyl;

[0240] Each R 3 and R 4 independently the same or different and are linear or branched 1-6 alkyl.

[0241] Preferably, R 3 The groups are the same. Preferably, R 4 The groups are the same.

[0242] Specific metallocene complexes of the present invention include:

[0243] Racemic-trans-dimethylsilanediyl[2-methyl-4,8-bis-(3',5'-dimethylphenyl)-1,5,6,7-tetrahydro-s-indacene-1-yl][2-methyl-4-(3',5'-dimethylphenyl)-5-methoxy-6-tert-butylindene-1-yl] hafnium dichloride (MC-1),

[0244] Racemic-trans-dimethylsilanediyl[2-methyl-4,8-bis-(4′-tert-butylphenyl)-1,5,6,7-tetrahydro-s-indacene-1-yl][2-methyl-4-(3′,5′-dimethyl-phenyl)-5-methoxy-6-tert-butylindene-1-yl] hafnium dichloride (MC-2),

[0245] Racemic-trans-dimethylsilanediyl[2-methyl-4,8-bis-(4′-tert-butylphenyl)-1,5,6,7-tetrahydro-s-indacene-1-yl][2-methyl-4-(4′-tert-butylphenyl)-5-methoxy-6-tert-butylinden-1-yl] hafnium dichloride (MC-3),

[0246] Racemic-trans-dimethylsilanediyl[2-methyl-4,8-bis-(3',5'-dimethylphenyl)-1,5,6,7-tetrahydro-s-indacene-1-yl][2-methyl-4-(3',5'-di-tert-butyl-phenyl)-5-methoxy-6-tert-butylinden-1-yl] hafnium dichloride (MC-4),

[0247] Racemic-trans-dimethylsilanediyl[2-methyl-4,8-bis-(3',5'-dimethylphenyl)-1,5,6,7-tetrahydro-s-indacene-1-yl][2-methyl-4-(4'-tert-butylphenyl)-5-methoxy-6-tert-butylindene-1-yl] hafnium dichloride (MC-5)

[0248] or its corresponding dimethyl analog.

[0249]

[0250] For the avoidance of doubt, any narrow definition of a substituent provided above may be combined with any other broad or narrow definition of any other substituent.

[0251] In the above disclosure, when a narrow definition of a substituent is given, that narrow definition is deemed to be disclosed together with all broad and narrow definitions of other substituents in this application.

[0252] synthesis

[0253] The required ligands for forming the catalyst of the present invention can be synthesized by any method, and a skilled organic chemist will be able to design various synthesis schemes for making the necessary ligand materials. WO2007 / 116034 discloses the chemical composition of the necessary substances, and is incorporated herein by reference. Synthesis schemes can also be found in WO2002 / 02576, WO2011 / 135004, WO2012 / 084961, WO2012 / 001052, WO2011 / 076780 and WO2015 / 158790 generally. The embodiment part also provides sufficient guidance for the technician.

[0254] Catalyst

[0255] In order to form the active catalytic species, it is generally necessary to use a co-catalyst which is well known in the art.

[0256] According to the present invention, a cocatalyst system comprising a boron-containing cocatalyst and / or an aluminoxane cocatalyst is used in combination with the metallocene catalyst complex defined above.

[0257] The aluminoxane cocatalyst may be any of the formula (X):

[0258]

[0259] wherein n is generally 6 to 20, and R has the following meanings.

[0260] Aluminoxanes are formed upon partial hydrolysis of organoaluminum compounds, such as those of the formula AlR3, AlR2Y, and Al2R3Y3, wherein R can be, for example, C1-C 10Alkyl, preferably C1-C5 alkyl, or C 3-10 Cycloalkyl, C7-C 12 Aralkyl or alkylaryl and / or phenyl or naphthyl, and wherein Y can be hydrogen, halogen, preferably chlorine or bromine, or C1-C 10 The alkoxy group is preferably a methoxy group or an ethoxy group. The oxygen-containing aluminoxane obtained is usually not a pure compound but a mixture of oligomers of the formula (X).

[0261] The preferred aluminoxane is methylaluminoxane (MAO).Since the aluminoxanes used as cocatalysts according to the invention are not pure compounds due to the way they are prepared, the molar concentrations of the aluminoxane solutions hereinafter are based on their aluminum content.

[0262] According to the present invention, a boron-containing cocatalyst may also be used instead of the aluminoxane cocatalyst, or the aluminoxane cocatalyst may be used in combination with the boron-containing cocatalyst.

[0263] Those skilled in the art will appreciate that in the case of a boron-based cocatalyst, the complex is usually pre-alkylated by reaction with an alkyl aluminum compound such as TIBA. This process is well known and any suitable aluminum alkyl, such as Al(C 1-6 Preferred alkylaluminum compounds are triethylaluminum, triisobutylaluminum, triisohexylaluminum, tri-n-octylaluminum and tri-isooctylaluminum.

[0264] Alternatively, when a borate cocatalyst is used, the metallocene catalyst complex is in its alkylated form, ie, for example, a dimethyl or dibenzyl metallocene catalyst complex may be used.

[0265] Boron-containing cocatalysts of interest include those of formula (Z)

[0266] BY3(Z)

[0267] Wherein Y is identical or different and is hydrogen atom, alkyl of 1 to about 20 carbon atoms, aryl of 6 to about 15 carbon atoms, alkylaryl, aralkyl, halogenated alkyl or halogenated aryl, each of which has 1 to 10 carbon atoms in alkyl and 6 to 20 carbon atoms in aryl or has fluorine, chlorine, bromine or iodine.Preferred examples of Y are trifluoromethyl, unsaturated groups such as halogenated aryl, such as p-fluorophenyl, 3,5-difluorophenyl, pentachlorophenyl, pentafluorophenyl, 3,4,5-trifluorophenyl and 3,5-bis(trifluoromethyl)phenyl.Preferred selection is trifluoroborane, tris(4-fluorophenyl)borane, tris(3,5-difluorophenyl)borane, tris(4-fluoromethylphenyl)borane, tris(2,4,6-trifluorophenyl)borane, tris(pentafluorophenyl)borane, tris(3,5-difluorophenyl)borane and / or tris(3,4,5-trifluorophenyl)borane.

[0268] Particularly preferred is tris(pentafluorophenyl)borane.

[0269] However, preference is given to using borates, i.e. compounds containing a borate anion. Such ionic promoters preferably contain a non-coordinating anion, for example tetrakis(pentafluorophenyl)borate. Suitable counterions are protonated amines or aniline derivatives, for example methylammonium, aniline, dimethylammonium, diethylammonium, N-methylaniline, diphenylammonium, N,N-dimethylaniline, trimethylammonium, triethylammonium, tri-n-butylammonium, methyldiphenylammonium, pyridinium, p-bromo-N,N-dimethylaniline or p-nitro-N,N-dimethylaniline.

[0270] Preferred ionic compounds that can be used according to the present invention include: tributylammonium tetrakis(pentafluorophenyl)borate, tributylammonium tetrakis(trifluoromethylphenyl)borate, tributylammonium tetrakis(4-fluorophenyl)borate, N,N-dimethylcyclohexylammonium tetrakis(pentafluorophenyl)borate, N,N-dimethylbenzylammonium tetrakis(pentafluorophenyl)borate, N,N-dimethylanilinium tetrakis(pentafluorophenyl)borate, N,N-di(propyl)ammonium tetrakis(pentafluorophenyl)borate, di(cyclohexyl)ammonium tetrakis(pentafluorophenyl)borate, triphenylphosphonium tetrakis(pentafluorophenyl)borate, triethylphosphonium tetrakis(pentafluorophenyl)borate, diphenylphosphonium tetrakis(pentafluorophenyl)borate, triphenylcarbonium tetrakis(pentafluorophenyl)borate, or ferrocene tetrakis(pentafluorophenyl)borate.

[0271] Preferred are triphenylcarbonium tetrakis(pentafluorophenyl)borate, N,N-dimethylanilinium tetrakis(pentafluorophenyl)borate, N,N-dimethylcyclohexylammonium tetrakis(pentafluorophenyl)borate and N,N-dimethylbenzylammonium tetrakis(pentafluorophenyl)borate.

[0272] Particularly preferred are triphenylcarbonium tetrakis(pentafluorophenyl)borate and N,N-dimethylanilinium tetrakis(pentafluorophenyl)borate.

[0273] Therefore, it is particularly preferred to use Ph3CB(PhF5)4 and the like.

[0274] According to the present invention, preferred cocatalysts are aluminoxanes, more preferably methylaluminoxane, combinations of aluminoxanes with alkylaluminum, boron or borate cocatalysts and combinations of aluminoxanes with boron-based cocatalysts.

[0275] According to the most preferred embodiment of the present invention, the preferred cocatalyst is an aluminoxane, most preferably a combination of methylaluminoxane and a borate cocatalyst such as N,N-dimethylammonium-tetrapentafluorophenylborate and Ph3CB(PhF5)4. The combination of methylaluminoxane and trityl borate is particularly preferred.

[0276] Suitable amounts of promoters are well known to the skilled person.

[0277] The molar ratio of the boron feed amount to the metal ion of the metallocene may be in the range of 0.1:1 to 10:1 mol / mol, preferably 0.3:1 to 7:1, especially 0.3:1 to 5:1 mol / mol.

[0278] The molar ratio of Al in the aluminoxane to the metal ion of the metallocene may be in the range of 1:1 to 2000:1 mol / mol, preferably 10:1 to 1000:1, more preferably 50:1 to 500:1 mol / mol.

[0279] The catalyst may contain 10 to 100 μmol of metal ions of the metallocene and 5 to 10 mmol of Al per gram of silica.

[0280] Catalyst preparation

[0281] The metallocene catalyst complexes of the present invention can be used as catalysts for propylene polymerization in combination with a suitable cocatalyst, for example in a solvent such as toluene or an aliphatic hydrocarbon, (ie for polymerization in solution), as is well known in the art.

[0282] The catalyst of the present invention can be used in a supported or unsupported form. Preferably, the catalyst system of the present invention is used in a supported form. The particle support material used is preferably an organic or inorganic material, such as silicon dioxide, aluminum oxide or zirconium oxide or a mixed oxide, such as silicon dioxide-alumina, in particular silicon dioxide, aluminum oxide or silicon dioxide-alumina. Preferably, a silicon dioxide support is used. The technician knows the procedures required for supporting the metallocene catalyst. Particularly preferably, the support is a porous material so that the complex can be loaded into the pores of the support, for example, using a method similar to that described in WO94 / 14856, WO95 / 12622 and WO2006 / 097497.

[0283] The average particle size of the silica support can generally be from 10 to 100 μm. However, it has proven to be particularly advantageous if the support has an average particle size of from 15 to 80 μm, preferably from 18 to 50 μm.

[0284] The average pore size of the silica support may be in the range of 10 to 100 nm, and the pore volume may be between 1 and 3 mL / g.

[0285] Examples of suitable support materials are silicas such as ES757 produced and sold by PQ Corporation, Sylopol 948 produced and sold by Grace or SUNSPERA DM-L-303 produced by AGC Si-Tech Co.

[0286] The support may optionally be calcined before use in catalyst preparation to achieve an optimum silanol group content.

[0287] The use of these vectors is routine in the art.

[0288] In an alternative embodiment, no support is used at all. Such catalysts can be prepared in solution, for example in an aromatic solvent such as toluene, by contacting the metallocene (as a solid or as a solution) with a cocatalyst, for example methylaluminoxane or borane or a borate predissolved in an aromatic solvent, or can be prepared by adding the dissolved catalyst components sequentially to the polymerization medium.

[0289] In one embodiment, no external support is used, but the catalyst is still present in the form of solid particles. Therefore, no external support material is used, such as an inert organic or inorganic support, such as silicon dioxide as described above, but an emulsion-curing method is used to prepare the solid catalyst. The full disclosure of the method is described in WO2003 / 051934, which is incorporated herein by reference.

[0290] In one embodiment, the preparation of the catalyst system according to the present invention comprises the following steps:

[0291] a) reacting a silica support with an aluminoxane cocatalyst in a suitable hydrocarbon solvent such as toluene and optionally with subsequent washing and drying to obtain an aluminoxane cocatalyst treated support,

[0292] b) reacting a metallocene complex of formula (I) with an aluminoxane cocatalyst in a suitable hydrocarbon solvent such as toluene,

[0293] c) adding a borate co-catalyst to the solution obtained in step b) to obtain a solution of a metallocene complex of formula (I), a borate co-catalyst and an aluminoxane co-catalyst, wherein the amount of the borate co-catalyst added is such that the boron / hafnium feed amount reaches a molar ratio of 0.1:1 to 10:1,

[0294] d) adding the solution obtained in step c) to the support treated with aluminoxane co-catalyst obtained in step a), wherein the amount of aluminoxane co-catalyst added in step a) is 75.0 wt % to 97.0 wt % of the total amount of aluminoxane co-catalyst and the amount of aluminoxane co-catalyst added in step b) is 3.0 wt % to 25.0 wt % of the total amount of aluminoxane co-catalyst;

[0295] and

[0296] e) optionally drying the supported catalyst system thus obtained.

[0297] polymerization

[0298] The heterophasic propylene copolymer is prepared in a multistage polymerization using conventional polymerization techniques, such as slurry or bulk polymerization, and at least one gas phase reactor. In the case of propylene polymerization for a slurry reactor, the reaction temperature is generally in the range of 60 to 110° C. (e.g. 60 to 90° C.), the reactor pressure is generally in the range of 5 to 80 bar (bar) (e.g. 20 to 60 bar), and the residence time is generally in the range of 0.1 to 5 hours (e.g. 0.3 to 2 hours). Monomers are generally used as reaction medium.

[0299] For gas phase reactors, the reaction temperature used is generally in the range of 60 to 115° C. (e.g., 70 to 110° C.), the reactor pressure is generally in the range of 10 to 25 bar (bar), and the residence time is generally 0.5 to 8 hours (e.g., 0.5 to 4 hours). The gas used will be the monomer, optionally as a mixture with a non-reactive gas such as nitrogen or propane. In addition to the actual polymerization step and reactor, the method may include any additional polymerization steps, such as a prepolymerization step, and any further reactor treatment steps known in the art. Typically, the amount of catalyst used depends on the properties of the catalyst, the reactor type and conditions, and the desired properties of the polymer product. As is well known in the art, hydrogen can be used to control the molecular weight of the polymer.

[0300] The polymerization in the process of the present invention can be carried out in two or more polymerization reactors, for example 2. The process may also involve a prepolymerization reaction. The prepolymerization step is a conventional step conventionally used in polymer synthesis and is different from the catalyst prepolymerization step discussed above.

[0301] Ideally, the process of the present invention uses two main reactors, a first reactor operating in bulk, and a gas phase reactor. The process may also use a prepolymerization step. Where a prepolymerization step is used, any weight percent of the product produced in that step is considered part of component (A) and should be taken into account when determining the weight percent of component (A).

[0302] The process of the invention preferably forms a first component (A), which may be a homopolymer, which is subsequently combined with the ethylene propylene copolymer amorphous part (B) to form the heterophasic copolymer of the invention. Component (B) is preferably formed a second time and preferably in the gas phase.

[0303] Ideally therefore, the propylene homopolymer matrix component (A) is formed in a bulk step and the propylene ethylene copolymer amorphous phase (B) is formed in a gas phase step.

[0304] Preferred polymerization methods include polymerization of:

[0305] (I) propylene and optionally ethylene to form a propylene homopolymer or a propylene ethylene copolymer component (A) having an ethylene content of up to 2% by weight; and then polymerizing

[0306] (II) propylene and ethylene, preferably in the gas phase, to form an ethylene-propylene rubber component (B) dispersed in a matrix;

[0307] wherein steps (I) and (II) are both carried out in the presence of a catalyst as defined herein.

[0308] application

[0309] The heterophasic polypropylene copolymers of the present invention can be used to manufacture articles, such as flexible pipes / tubes, profiles, cable insulation, sheets or films. These articles can be used in the medical and general packaging fields, and can also be used for technical purposes such as power cables or geomembranes. Alternatively, the heterophasic polypropylene copolymers can be used for impact modification of compositions for injection molding of articles, for example for technical applications in the automotive field.

[0310] For impact modification the inventive heterophasic polypropylene copolymer can be blended with another polypropylene copolymer. Accordingly, the present invention also relates to polymer blends comprising the inventive heterophasic polypropylene copolymer.

[0311] The polymers of the present invention can be used to make a variety of final products, such as films (cast, blown or BOPP films), molded products (such as injection molded, blown, rotomolded products), extrusion coatings, etc. Preferably, the articles comprising the films of the present invention are used for packaging. Packaging of interest includes heavy-duty bags, hygiene films, laminated films, and flexible packaging films.

[0312] The invention will now be illustrated by reference to the following non-limiting examples.

[0313] Analytical Testing

[0314] Measurement method:

[0315] Determination of Al, Zr and Hf (ICP method)

[0316] In a glove box, an aliquot of the catalyst (approximately 40 mg) was weighed onto a glass weighing boat using an analytical balance. The sample was then exposed to air overnight while being placed in a steel secondary container equipped with an air inlet. The contents of the boat were then rinsed into an Xpress microwave container (20 mL) with 5 mL of concentrated nitric acid (65%). The sample was then subjected to microwave-assisted digestion at 150°C for 35 minutes using a MARS 6 laboratory microwave unit. The digested sample was cooled for at least 4 hours and then transferred to a 100 mL volume glass volumetric glass flask. A standard solution containing 1000 mg / LY and Rh (0.4 mL) was added. The flask was then filled with distilled water and shaken thoroughly. The solution was filtered through a 0.45 μm nylon syringe filter and then analyzed using a Thermo iCAP 6300ICP-OES and iTEVA software.

[0317] The instrument was calibrated for Al, B, Hf, Mg, Ti and Zr using a blank (5% HNO3 solution) and six standards of 0.005 mg / L, 0.01 mg / L, 0.1 mg / L, 1 mg / L, 10 mg / L and 100 mg / L of Al, B, Hf, Mg, Ti and Zr in 5% HNO3 distilled water. However, not every calibration point is used for every wavelength. Each calibration solution contains 4 mg / L of Y and Rh standards. Al 394.401 nm was calibrated using the following calibration points: blank, 0.1 mg / L, 1 mg / L, 10 mg / L and 100 mg / L. Using blank, 0.01 mg / L, 0.1 mg / L, 1 mg / L, 10 mg / L and 100 mg / L standards, Al 167.079 nm was calibrated to Al 394.401 nm, excluding 100 mg / L and Zr 339.198 nm. The calibration curve used curve fitting and 1 / concentration weighting. Using blank, 0.01 mg / L, 0.1 mg / L, 1 mg / L, 10 mg / L and 100 mg / L standards, Hf 264.141 nm was calibrated.

[0318] Immediately prior to analysis, the calibration was verified and adjusted (instrument slope function) using blanks and 10 mg / L Al, B, Hf, Mg, Ti, and Zr standards with 4 mg / L Y and Rh. Quality control samples (QC: 1 mg / L Al, Au, Be, Hg, and Se; 2 mg / L Hf and Zr, 2.5 mg / L As, B, Cd, Co, Cr, Mo, Ni, P, Sb, Sn, and V; 4 mg / L Rh and Y; 5 mg / L Ca, K, Mg, Mn, Na, and Ti; 10 mg / L Cu, Pb, and Zn; 25 mg / L Fe and 37.5 mg / L Ca in 5% HNO3 in distilled water) were run to confirm the reset slopes for Al, B, Hf, Mg, Ti, and Zr. QC samples were also run at the end of the scheduled analytical set.

[0319] The Zr 339.198nm{99} line was used to monitor the Zr content. The Hf 264.141nm{128} line was used to monitor the Hf content. When the Al concentration in the test part was lower than 2wt%, the aluminum content was monitored by the 167.079nm{502} line, and when the Al concentration was higher than 2wt%, the 394.401nm{85} line was used. Y 371.030nm{91} was used as an internal standard for Zr 339.198nm and Al 394.401nm, and Y 224.306nm{450} was used for Al 167.079nm.

[0320] The reported values ​​were back-calculated to the original catalyst sample using the original mass of the catalyst aliquot and the dilution volume.

[0321] GPC: average molecular weight, molecular weight distribution and polydispersity index (Mn, Mw, Mw / Mn)

[0322] The average molecular weights (Mw and Mn), the molecular weight distribution (MWD) and its breadth (described by the polydispersity index), PDI = Mw / Mn (wherein Mn is the number average molecular weight and Mw is the weight average molecular weight) are determined by gel permeation chromatography (GPC) according to ISO 16014-1:2003, ISO 16014-2:2003, ISO 16014-4:2003 and ASTM D 6474-12.

[0323] A high temperature GPC instrument equipped with an infrared (IR) detector (IR4 or IR5 from PolymerChar (Valencia, Spain)) or a differential refractometer (RI) from Agilent Technologies, three Agilent-PLgel Olexis columns and one Agilent-PLgel Olexis Guard column was used. 1,2,4-Trichlorobenzene (TCB) stabilized with 250 mg / L 2,6-di-tert-butyl-4-methylphenol was used as solvent and mobile phase. The chromatographic system was operated at 160 °C and a constant flow rate of 1 mL / min. 200 μL of sample solution was injected for each analysis. Data collection was performed using Agilent Cirrus software version 3.3 or PolymerCharGPC-IR control software.

[0324] The column set was calibrated using a universal calibration method (according to ISO 16014-2:2003) with 19 narrow MWD polystyrene (PS) standards ranging from 0.5 kg / mol to 11 500 kg / mol. The PS standards were allowed to dissolve at room temperature for several hours. The conversion of polystyrene peak molecular weight to polyolefin molecular weight was accomplished by using the Mark Houwink equation and the following Mark Houwink constant:

[0325] K PS =19x10 -3 mL / g, α PS =0.655

[0326] K PE =39x10 -3 mL / g, α PE =0.725

[0327] K PP =19x10 -3 mL / g, α PP =0.725

[0328] A third-order polynomial fit was used to fit the calibration data.

[0329] All samples were prepared at concentrations ranging from 0.5-1 mg / ml and dissolved at 160°C for 2.5 hours (for PP) or 3 hours.

[0330] DSC analysis

[0331] DSC analysis was performed on 5 to 7 mg samples using a Mettler TA Instruments Q2000 differential scanning calorimeter (DSC). DSC was run in the temperature range of -30°C to +225°C with a heating / cooling / heating cycle with a scanning rate of 10°C / min according to ISO 11357 / Part 3 / Method C2. The crystallization temperature (Tc) was determined from the cooling step, while the main melting temperature (Tm) and the heat of fusion (H m ) is determined by the second heating step.

[0332] Melt flow rate

[0333] Melt flow rate (MFR) is determined according to ISO 1133 and is expressed in g / 10 min. MFR is an indicator of polymer fluidity and processability. The higher the melt flow rate, the lower the viscosity of the polymer. MFR is measured at 230°C and a load of 2.16 kg (MFR2).

[0334] Determination of xylene soluble fraction (XS):

[0335] The xylene soluble fraction (XS) defined and described in the present invention is determined according to ISO 16152 as follows: 2.0 g of polymer are dissolved in 250 ml of p-xylene at 135° C. under stirring. After 30 minutes, the solution is allowed to cool for 15 minutes at ambient temperature and then allowed to stand for 30 minutes at 25±0.5° C. The solution is filtered into two 100 ml flasks using filter paper. The solution from the first 100 ml container is evaporated in a stream of nitrogen and the residue is dried under vacuum at 90° C. until constant weight is reached. The xylene soluble fraction (weight percentage) can then be determined as follows:

[0336] XSwt-%=(100x m1 x v0) / (m0 x v1),

[0337] Where m0 represents the initial polymer amount (g), m1 defines the weight of the residue (g), v0 defines the initial volume (ml), and v1 defines the volume of the analyzed sample (ml).

[0338] CRYSTEX

[0339] Crystalline and soluble fractions and their respective properties

[0340] The crystalline (CF) and soluble fractions (SF) of the polypropylene (PP) compositions as well as the comonomer content and intrinsic viscosity of each fraction were analyzed by CRYSTEX QC, Polymer Char (Valencia, Spain).

[0341] Demonstration of the CRYSTEX QC instrument Del Hierro, P.; Ortin, A.; Monrabal, B.; 'Analysis of the soluble fraction in polypropylene, Column, February 2014, pp. 18-23. The crystalline and amorphous fractions are separated by temperature cycles of dissolution at 160°C, crystallization at 40°C and redissolution in 1,2,4-trichlorobenzene (1,2,4-TCB) at 160°C. The quantification of SF and CF as well as the determination of the ethylene content (C2) are carried out by means of an infrared detector (IR4) and an online double capillary viscometer for the determination of the intrinsic viscosity (IV).

[0342] The IR4 detector is a multi-wavelength detector that detects IR absorbance in two different bands (CH3 and CH2) and is used to determine the concentration and ethylene content in ethylene-propylene copolymers. The IR4 detector is calibrated using a series of EP copolymers with known ethylene contents ranging from 2-wt% to 69-wt% (determined by 13C-NMR).

[0343] The amounts of the soluble fraction (SF) and the crystalline fraction (CF) are related by means of an XS calibration to the amount of "xylene cold solubles" (XCS) and the xylene cold insolubles (XCI) fraction determined by the standard gravimetric method according to ISO 16152. The XS calibration was achieved by testing various EP copolymers with XS contents ranging from 2 to 31 wt%.

[0344] The intrinsic viscosity (IV) of the parent EP copolymer and its soluble and crystalline fractions were determined using an online dual capillary viscometer and correlated to the corresponding IV measured in decalin according to ISO 1628.

[0345] Calibration was achieved using several commercial EP PP copolymers with IV = 2-4 dL / g.

[0346] A sample of the PP composition to be analyzed was weighed out at a concentration of 10 to 20 mg / ml. After automatically filling a vial with 1,2,4-TCB containing 250 mg / l of 2,6-tert-butyl-4-methylphenol (BHT) as an antioxidant, the sample was dissolved at 160°C with continuous stirring at 800 rpm until completely dissolved (usually for 60 minutes).

[0347] A defined volume of the sample solution is injected into a chromatographic column filled with an inert support, where crystallization of the sample and separation of the soluble fraction from the crystalline fraction is performed. This process is repeated twice. During the first injection, the entire sample is measured at high temperature to determine the IV [dl / g] and C2 [wt%] of the PP composition. During the second injection, the soluble fraction (at low temperature) and the crystalline fraction (at high temperature) accompanying the crystallization cycle are measured (wt% SF, wt% C2, IV).

[0348] Flexural modulus was determined using ISO 178 and was measured on samples prepared according to injection molded samples as described in EN ISO 1873-2 (80 x 10 x 4 mm).

[0349] Charpy notched impact strength

[0350] Charpy notched impact strength was measured according to ISO 179 1eA at 23°C and -20°C (after conditioning for 96 hours at 23°C and 50% relative humidity) using 80x10x4mm 3 The test bars were injection molded in accordance with EN ISO 1873-2.

[0351] Dynamic Mechanical Analysis (DMA)

[0352] The glass transition temperature Tg and the storage modulus (G') were determined by dynamic mechanical analysis according to ISO 6721-7. Compression molded samples (40 x 10 x 1 mm2) were prepared between -100 °C and +150 °C at a heating rate of 2 °C / min and a frequency of 1 Hz. 3 ) are measured in torsion mode.

[0353] Intrinsic viscosity (IV)

[0354] The intrinsic viscosity (IV) value increases with the molecular weight of the polymer. The IV value is measured in decalin at 135°C according to ISO 1628 / 1.

[0355] Quantifying copolymer microstructure using NMR spectroscopy

[0356] Quantitative 13C{1H} NMR spectra were recorded in solution using a Bruker Avance III 400 NMR spectrometer at 400.15 and 100.62 MHz for 1H and 13C, respectively. Nitrogen was used for all pneumatics and all spectra were recorded at 125°C using a 13C optimized 10 mm extended temperature detector. Approximately 200 mg of material was dissolved in 3 ml of 1,2-tetrachloroethane-d2 (TCE-d2) along with chromium (III) acetylacetonate (Cr(acac)3) to form a 65 mM solution of the relaxant in the solvent as described in G. Singh, A. Kothari, V. Gupta, Polymer Test 2009, 28(5), 475. To ensure homogeneity of the solution, the NMR tube was further heated in a rotary oven for at least 1 hour after initial sample preparation in a heating block. After insertion of the magnet, the tube was rotated at a frequency of 10 Hz. This setup is primarily to obtain the high resolution and quantification required for accurate ethylene content quantification. As described in Z. Zhou, R. Kuemmerle, X. Qiu, D. Redwine, R. Cong, A. Taha, D. Baugh, B. Winniford, J. Mag. Reson. 187 (2007) 225 and V. Busico, P. Carbonniere, R. Cipullo, C. Pellecchia, J. Severn, G. Talarico, Macromol. Rapid Commun. 2007, 28, 1128, standard single pulse excitation was used in the absence of NOE, using an optimized tip angle, 1 second cycle delay and a dual-level WALTZ16 decoupling scheme. A total of 6144 (6k) transients were obtained for each spectrum. The quantitative 13C{1H} NMR spectra were processed, integrated, and relevant quantitative properties were determined from the integrals. All chemical shifts are indirectly referenced to the central methylene group of the ethylene block (EEE) at 30.00 ppm using the chemical shift of the solvent. This approach allows for comparative reference even when this building block is not present.

[0357] Characteristic signals corresponding to 2,1 red regional defects were observed (as described in L. Resconi, L. Cavallo, A. Fait, F. Piemontesi, Chem. Rev. 2000, 100 (4), 1253, Cheng, HN, Macromolecules 1984, 17, 1950, and WJ. Wang and S. Zhu, Macromolecules 2000, 33 1157), and corrections for the effects of regional defects on the properties determined were required. Characteristic signals corresponding to other types of regional defects were not observed.

[0358] Characteristic signals corresponding to the incorporation of ethylene were observed (as described in Cheng, HN, Macromolecules 1984, 17, 1950) and the comonomer fraction, ie the fraction of ethylene in the polymer relative to all monomers in the polymer, was calculated:

[0359] fE=(E / (P+E).

[0360] The comonomer fraction was quantified using the method of Wang et al. by integrating multiple signals over the entire spectral region of the 13C{1H} spectrum (WJ. Wang and S. Zhu, Macromolecules 2000, 33 1157). This method was chosen because of its robustness and ability to account for the presence of regional defects when necessary. The integration region was slightly adjusted to improve applicability over the entire range of comonomer content.

[0361] Calculate the mole percentage of comonomer incorporation based on the mole fraction:

[0362] E[mol%]=100*fE

[0363] Calculate the weight percent of comonomer incorporation based on the mole fraction:

[0364] E[wt%]=100*(fE*28.06) / ((fE*28.06)+((1-fE)*42.08)). Example

[0365] Metallocene synthesis

[0366] Chemicals used for complex preparation:

[0367] 2,6-Dimethylaniline (Acros), 1-bromo-3,5-dimethylbenzene (Acros), 1-bromo-3,5-di-tert-butylbenzene (Acros), bis(2,6-diisopropylphenyl)imidazolium chloride (Aldrich), triphenylphosphine (Acros), NiCl2(DME)(Aldrich), dichlorodimethylsilane (Merck), ZrCl4(Merck), trimethyl borate (Acros), Pd(OAc)2(Aldrich), NaBH4(Acros), 2.5M nBuLi hexane solution (Chemetal), CuCN(Merck), magnesium turnings (Acros), silica gel 60, 40-63μm (Merck), bromine (Merck), 96% sulfuric acid (Reachim), sodium nitrite (Merck), copper powder (Alfa), potassium hydroxide (Merck), K2CO3(Merck), 12M HCl (Reachim), TsOH (Aldrich), MgSO4 (Merck), Na2CO3 (Merck), Na2SO4 (Akzo Nobel), methanol (Merck), ether (Merck), 1,2-dimethoxyethane (DME, Aldrich), 95% ethanol (Merck), dichloromethane (Merck), hexane (Merck), THF (Merck) and toluene (Merck) were used as received. Hexane, toluene and dichloromethane used for organometallic synthesis were dried over molecular sieve 4A (Merck). Ether, THF and 1,2-dimethoxyethane used for organometallic synthesis were distilled over sodium benzophenone. CDCl3 (Deutero GmbH) and CD2Cl2 (Deutero GmbH) were dried over molecular sieve 4A.

[0368] 4,8-Dibromo-1-methoxy-2-methyl-1,2,3,5,6,7-hexahydro-s-indacene and 5-tert-butyl-7-(3,5-di-tert-butylphenyl)-6-methoxy-2-methyl-1H-indene were obtained as described in WO2015 / 158790.

[0369] Synthesis of MC1 (metallocene of the present invention)

[0370] 4,8-Bis(3,5-dimethylphenyl)-6-methyl-1,2,3,5-tetrahydro-s-indacene

[0371]

[0372] To a mixture of 2.0 g (2.56 mmol) NiCl2(PPh3)IPr and 36.3 g (100.8 mmol) 4,8-dibromo-1-methoxy-2-methyl-1,2,3,5,6,7-hexahydro-s-indacene, 500 ml (250 mmol, 2.5 equivalents) of 0.5 M THF solution of 3,5-dimethylphenylmagnesium bromide was added at a rate to maintain gentle reflux (maintained for about 15 minutes). The resulting solution was refluxed for another hour, then cooled to room temperature, and 1200 ml of 0.5 M HCl and 500 ml of dichloromethane were added. The organic layer was separated, dried over K2CO3, passed through a short pad of silica gel 60 (40-63 μm, about 30 ml), and then evaporated to dryness to give a crude mixture of diastereomers of 4,8-bis(3,5-dimethylphenyl)-1-methoxy-2-methyl-1,2,3,5,6,7-hexahydro-s-indacene as a brown oil. Further, 315 mg of TsOH was added to a solution of the crude product in 420 ml of toluene, and the resulting mixture was refluxed for 10 minutes using a Dean-Stark head. Then, another portion of 220 mg of TsOH was added, and the resulting mixture was refluxed for 10 minutes. Finally, the last operation was repeated with 50 mg of TsOH. After cooling to room temperature, the reaction mixture was washed with 200 ml of 10% K2CO3. The organic layer was separated, and the aqueous layer was extracted with an additional 200 ml of dichloromethane. The combined organic extracts were dried over anhydrous K2CO3 (the organic layer turned dark red at this stage), passed through a short pad of silica gel 60 (40-63 μm, 30 ml), and the resulting light yellow solution was evaporated to about 30 ml to give a solution containing a large amount of white precipitate. 300 ml of n-hexane was added to the mixture. The precipitated solid (G3) was filtered out, washed with n-hexane, and dried in vacuo. The procedure gave 29.33 g (77.48 mmol, 76.9%) of 4,8-bis(3,5-dimethylphenyl)-6-methyl-1,2,3,5-tetrahydro-s-indacene as a white fine crystalline solid. The mother liquor was evaporated to dryness to give a light yellow solid block. The solid block was ground with 40 ml of warm n-hexane, cooled to room temperature, and filtered (G3). The resulting solid was washed with n-hexane and dried in vacuo. This procedure additionally gave 4.55 g (12.02 mmol, 11.9%) of 4,8-bis(3,5-dimethylphenyl)-6-methyl-1,2,3,5-tetrahydro-s-indacene as a white powder. The total yield of the title product was therefore 33.88 g (89.5 mmol, 88.8%).

[0373] 1H NMR(CDCl3): δ7.04(s,2H),7.03(s,2H),6.98(s,2H),6.43(m,1H),3.23(s,2H),2.89(t,J=7.3H z, 2H), 2.83 (t, J = 7.3Hz, 2H), 2.38 (s, 6H), 2.37 (s, 6H), 2.04 (s, 3H), 1.99 (quint, J = 7.3Hz, 2H). 13 C{ 1 H}NMR(CDCl3): δ145.38,142.84,140.85,140.43,140.21,139.80,138.37,137.55,137.39,133. 44,129.64,128.39,128.19,127.31,126.61,126.34,42.49,32.76,32.51,26.08,21.43,16.81.

[0374] [4,8-Bis(3,5-dimethylphenyl)-2-methyl-1,5,6,7-tetrahydro-s-indacen-1-yl]chlorodimethylsilane

[0375]

[0376] A suspension of 11.96 g (31.59 mmol) of 4,8-bis(3,5-dimethylphenyl)-6-methyl-1,2,3,5-tetrahydro-s-indacene in a mixture of 250 ml of ether and 40 ml of THF was cooled to -30°C, and 13.0 ml (31.59 mmol) of 2.43 M n BuLi hexane solution. The resulting mixture was stirred at room temperature overnight, then the resulting light orange solution containing a large amount of orange precipitate was cooled to -50 ° C, and 19.0 ml (20.33 g, 157.5 mmol, 4.99 equiv) of dichlorodimethylsilane was added in one go. The mixture was stirred at room temperature overnight, then filtered with a glass frit (G3), and the flask and filter cake were rinsed with 50 ml of toluene. The filtrate was evaporated to dryness to give 14.9 g (~100%) of the title compound as a white solid block, which was used further without additional purification.

[0377] 1H NMR(CDCl3): δ7.09(s,2H),7.02-6.94(m,4H),6.51(m,1H),4.07(s,1H),3.26-3.14(m, 1H), 2.95-2.79 (m, 2H), 2.60 (ddd, J=12.4Hz, J=8.4Hz, J=4.1Hz, 1H), 2.38 and 2.37 (2s, sum 12H),2.24(s,3H),2.12-1.99(m,1H),1.95-1.80(m,1H),-0.16(s,3H),-0.20(s,3H). 13 C{ 1 H}NMR(CDCl3): δ146.19,143.17,140.68,140.29,139.94,139.92,138.37,137.59,137.42,132.60,129.8 6,128.52,128.24,127.85,127.28,126.32,49.67,33.33,32.73,26.15,21.45,21.42,18.10,3.92,-1.45.

[0378] [4,8-Bis(3,5-dimethylphenyl)-2-methyl-1,5,6,7-tetrahydro-s-indacene-1-yl][6-tert-butyl-4-(3,5-dimethylphenyl)-5-methoxy-2-methyl-1H-indene-1-yl]dimethylsilane

[0379]

[0380] A solution of 10.13 g (31.59 mmol) of 5-tert-butyl-7-(3,5-dimethylphenyl)-6-methoxy-2-methyl-1H-indene (produced as described above for MC-1) in 250 ml of diethyl ether was cooled to -30°C, and 13.0 ml (31.59 mmol) of 2.43 M nBuLi hexane solution. The mixture was stirred at room temperature overnight, then the resulting light orange solution containing a small amount of precipitate was cooled to -45 ° C, and 200 mg CuCN was added. The resulting mixture was stirred at 25 ° C for 0.5 hours, and then 14.9 g (31.59 mmol) of [4,8-bis (3,5-dimethylphenyl) -2-methyl-1,5,6,7-tetrahydro-s-indacene-1-yl] chlorodimethylsilane (prepared as above) in 200 ml of THF was added in one go. The mixture was stirred at room temperature overnight, then filtered through a short pad of silica gel 60 (40-63 μm) and washed with 2x50 ml of dichloromethane. The combined organic eluents were evaporated to dryness and the residue was dried in vacuo at elevated temperature to give 24.0 g (about 100% or about 90% purity) of the title product (about 55:45 stereoisomer mixture) as a pale yellow solid foam, which was used further without additional purification.

[0381] 1 H NMR (CDCl3): δ 7.27 and 7.25 (2s, sum 2H), 7.04 (s, 4H), 6.98, 6.95 and 6.93 (3s, sum 3H), 6.90 and 6.85 (2s, sum 1H), 6.46 (s, 1H), 6.23 and 6.20 (2s, sum 1H), 4.41 and 4.16 (2s, sum 1H), 3.30-2.62 (m, 1H), 3.22 and 3.20 (2s, sum 3H), 3.04-2.79 (m, 2H), 2.68-2.56 (m, 1H), 2.39 (s, 6H), 2.35 (s, 9H), 2.32 (s, 3H), 2.18-1.80 (6s and 2m, sum 9H), 1.44 and 1.38 (2s, sum9H), -0.52, -0.58, -0.62 and -0.73 (4s, sum 6H).

[0382] trans-Dimethylsilanediyl[2-methyl-4,8-bis(4-tert-butylphenyl)-1,5,6,7-tetrahydro-s-indacene-1-yl][2-methyl-4-(3,5-dimethylphenyl)-5-methoxy-6-tert-butylindene-1-yl]hafnium dichloride

[0383]

[0384] Will nBuLi hexane solution (2.43M, 32.2ml, 78.25mmol) was added in one portion to a pale yellow solution of [2-methyl-4,8-bis(3,5-dimethylphenyl)-1,5,6,7-tetrahydro-s-indacene-1-yl][2-methyl-4-(3,5-dimethylphenyl)-5-methoxy-6-tert-butyl-1H-inden-1-yl]dimethylsilane (29.5g, 39.07mmol, 95% purity, prepared as described above) in 250ml of ether (cooled to -50°C). The mixture was stirred at room temperature for 5.5 hours, then the resulting deep red solution was cooled to -50°C and HfCl4 (12.52g, 39.09mmol) was added. The reaction mixture was stirred at room temperature for 24 hours to obtain a red solution containing a LiCl precipitate. The mixture was evaporated to dryness, 150ml of THF was added to the residue, and the resulting mixture was heated at 65°C for 24 hours. The mixture thus obtained is evaporated to dryness, the residue is dissolved in 100 ml of warm toluene, the suspension thus obtained is filtered through a glass frit (G4), and the filter cake is washed with 10 ml of toluene. The solution is evaporated to dryness and the residue is dissolved in 50 ml of hot n-hexane. The fine yellow crystalline solid precipitated from the solution at room temperature is collected and dried in vacuo. This process yields 16.6 g of trans-hafnocene dichloride, containing about 1.1 mol of n-hexane per mol of complex (or 1.4 g of n-hexane), so that the net weight of the isolated trans complex after adjustment is 15.2 g (39%). The mother liquor is evaporated to dryness and the residue is dissolved in 60 ml of n-pentane. The yellow powder obtained by precipitation from the solution at -30°C for several days is filtered off (G4) and then dried in vacuo to obtain 9.4 g of the target trans complex, which is contaminated with about 5% of unknown complexes and contains about 0.6 equivalents of n-hexane per equivalent of the target complex. The total isolated pure trans-MC1 corresponded to 62% isolated yield.

[0385] Comparison with Metallocene (MCC)

[0386] trans-Dimethylsilanediyl[2-methyl-4,8-bis(3,5-dimethylphenyl)-1,5,6,7-tetrahydro-s-indacene-1-yl][2-methyl-4-(3,5-dimethylphenyl)-5-methoxy-6-tert-butylindene-1-yl]zirconium dichloride (MCC)

[0387]

[0388] To a slightly turbid pale yellow solution of 23.06 g (30.54 mmol) of [4,8-bis(3,5-dimethylphenyl)-2-methyl-1,5,6,7-tetrahydro-s-indacen-1-yl][6-tert-butyl-4-(3,5-dimethylphenyl)-5-methoxy-2-methyl-1H-inden-1-yl]dimethylsilane in 250 ml of diethyl ether (cooled to -30°C) was added 25.1 ml (60.99 mmol) of 2.43 M n BuLi hexane solution. The mixture was stirred at room temperature for 5.5 hours, and then the resulting red solution was cooled to -50 ° C, and 7.12g (30.55mmol) ZrCl4 was added. The reaction mixture was stirred at room temperature for 24 hours to obtain a dark red solution containing a LiCl precipitate. According to the NMR spectrum, the solution contained a mixture of about 85 / 15 trans-dichlorodichlorobenzene zirconocene and cis-dichlorodichlorobenzene zirconocene, which contained some other impurities. The mixture was evaporated to dryness (to a red foam state), and the residue was treated with 100ml warm toluene. The resulting suspension was filtered through a glass frit (G4), and the filter cake was washed with 2x50ml warm toluene. The filtrate was evaporated to dryness, and the residue was dissolved in 70ml hot n-hexane. The light orange precipitate falling from the solution at room temperature overnight was collected and vacuum dried. This procedure yielded 7.8 g of trans-dimethylsilanediyl[2-methyl-4,8-di(3,5-dimethylphenyl)-1,5,6,7-tetrahydro-s-indacen-1-yl][2-methyl-4-(3,5-dimethylphenyl)-5-methoxy-6-tert-butylinden-1-yl]zirconium dichloride, containing about 1.0 mol of n-hexane per mole of complex, so that the adjusted net weight of the isolated trans complex was 7.13 g (26%). The mother liquor was evaporated to about 60 ml. The light orange powder precipitated from the solution at -25°C overnight was collected and dried in vacuo. This procedure produced 8.6 g of trans-dimethylsilanediyl[2-methyl-4,8-bis(3,5-dimethylphenyl)-1,5,6,7-tetrahydro-s-indacen-1-yl][2-methyl-4-(3,5-dimethylphenyl)-5-methoxy-6-tert-butylinden-1-yl]zirconium dichloride, containing about 0.75 mol of n-hexane per mole of complex (or 0.57 g of n-hexane in 8.6 g of product), so that the adjusted net weight of the isolated trans complex was 8.03 g (29%).

[0389] trans-dimethylsilanediyl[2-methyl-4,8-di(3,5-dimethylphenyl)-1,5,6,7-tetrahydro-s-indacene-1-yl][2-methyl-4-(3,5-dimethylphenyl)-5-methoxy-6-tert-butylinden-1-yl]zirconium dichloride x 1.0 n-hexane.

[0390] C 54 H60 Cl2OSiZr x C6H 14 Calculated for: C, 71.96; H, 7.45. Found: C, 72.30; H, 7.69.

[0391] 1 H NMR (CDCl3): δ7.55-6.90 (extremely broad single peak, 4H), 7.39 (s, 1H), 7.10 (s, 1H), 7.03 (s, 1H), 6.98 (s, 1H), 6.95 (s, 1H), 6.94 (s, 1H), 6.81 (s, 1H), 6.58 (s, 1H), 3.41 (s, 3H), 3.15-3.01 (m, 2H), 2.93 (ddd, J=16 .0Hz,8.1Hz,3.3Hz,1H),2.51-2.41(m,1H),2.39(s,3H),2.36(s,3H),2.34(s,12H),2.30(s,3 H),2.04(s,3H),2.07-1.95(m,1H),1.85-1.68(m,1H),1.35(s,9H),1.14(s,3H),-0.13(s,3H). 13 C{ 1 H}NMR (CDCl3): δ159.87,144.73,144.10,143.25,141.39,138.39,138.08,137.81,137.47,13 6.90,134.61,134.39,134.26,132.05,131.96,131.74,131.11,128.96,128.91,128.82,128. 74,127.74,127.44,127.01(broad single peak),126.76,123.42,123.12,121.60,121.08,82.55,81.91,62.67,35.68,33.87,32.39,30.39,26.04,21.53,21.47,21.41,21.24,19.78,18.60,3.62,1.70.

[0392] Preparation of MAO-silica carrier

[0393] The steel reactor equipped with a mechanical stirrer and a filter screen is flushed with nitrogen, and the reactor temperature is set to 20°C. Then, the silica grade DM-L-303 (7.4kg) pre-calcined at 600°C from AGC Si-Tech Co is added from the feed barrel, then carefully pressurized using a manual valve and decompressed with nitrogen. Then toluene (32.2kg) is added. The mixture is stirred (40rpm) for 15 minutes. Then, in 70 minutes, 30% by weight of MAO toluene (17.5kg) solution from Lanxess is added through the 12mm feed line at the top of the reactor. Then the reaction mixture is heated to 90°C and stirred for another two hours at 90°C. The slurry is settled and the mother liquor is filtered out. At 90°C, the solid is washed twice with toluene (32.2kg), then settled and filtered. The reactor is cooled to 60°C and the solid is washed with heptane (32.2kg).

[0394] Finally, the solid was dried at 60°C for 2 h under a nitrogen flow of 2 kg / h and a pressure of 0.3 barg, then dried under vacuum (-0.5 barg) for 5 h with stirring at 5 rpm. The solid MAO-silica support was collected as a free-flowing white powder containing 12.7 wt% Al.

[0395] Catalyst preparation

[0396] Catalyst CE1a (Comparative Example). In a glove box filled with nitrogen, anhydrous toluene (2.3 mL) solution of 0.2 mL MAO (30% weight toluene solution, AXION 1330CA Lanxess) was added to an aliquot (24.9 mg, 27 μmol) of metallocene MCC. The mixture was stirred at room temperature for 60 minutes. Next, 2.0 g of MAO-treated silica prepared as described above was placed in a glass reactor equipped with a porous glass frit. Then within 5 minutes, the solution of metallocene and MAO in toluene was slowly added to the carrier with gentle mixing. The resulting mixture was fully shaken and placed overnight. Anhydrous toluene (10 mL) was then added, and the slurry was fully mixed with an inert gas sprayed through a filter within 10 minutes. The solid was allowed to settle, and the liquid was filtered out and discarded. The resulting filter cake was vacuum dried for 1 hour to obtain 1.9 g of catalyst, which was a pink free-flowing powder.

[0397] Catalyst CE1b (Comparative)

[0398] A 30 wt % solution of MAO in toluene (0.7 kg) was added to a steel nitrogen blanket reactor by a burette at 20°C. Toluene (5.4 kg) was then added under stirring. Metallocene MCC (93 g) was added from a metal cylinder and then rinsed with 1 kg of toluene. The mixture was stirred for 60 minutes at 20°C. Triphenylcarbonium tetrakis(pentafluorophenyl)borate (91 g) was then added from a metal cylinder and subsequently rinsed with 1 kg of toluene. The mixture was stirred for more than 1 hour at room temperature. The resulting solution was added to the stirred filter cake of the MAO-silica support prepared as described above. The filter cake was allowed to stand for 12 hours, then dried for 2 hours at 60°C and N2 gas flow, and dried for another 5 hours under vacuum (-0.5 bar (barg)) with stirring.

[0399] The dried catalyst was sampled as a pink free-flowing powder containing 13.9% Al and 0.11% Zr.

[0400] Catalyst IE1a (invention).

[0401] In a glove box filled with nitrogen, 0.2mL MAO (30% weight toluene solution, AXION 1330CALanxess) was added to an aliquot (29.7mg, 27μmol) of metallocene MC1 in anhydrous toluene (2.3mL) solution. The mixture was stirred at room temperature for 30 minutes. Then triphenylcarbonium tetrakis (pentafluorophenyl) borate (25.6mg, 28μmol) was added to the mixture, and the mixture was stirred for 30 minutes. Then, 2.0g of the MAO-silica carrier prepared as described above was placed in a glass reactor equipped with porous glass frit. Then within 5 minutes, the solution of metallocene and MAO in toluene was slowly added to the carrier with gentle mixing. The resulting mixture was fully shaken and placed overnight. Then anhydrous toluene (10mL) was added, and the slurry was fully mixed with the inert gas sprayed by the filter screen within 10 minutes. Solid sedimentation was made, and the liquid was filtered out and discarded. The resulting filter cake was dried under vacuum for 1 hour to yield 1.9 g of catalyst as a yellow free-flowing powder.

[0402] Table 1a: Catalyst summary:

[0403]

[0404] (*) molar ratio of boron to transition metal; (**) calculated metallocene content in the catalyst

[0405] Table 1b: Catalyst summary:

[0406]

[0407] We have also compared the properties of the copolymers of the present invention with heterophasic polypropylene copolymers prepared using Ziegler-Natta catalysis.

[0408] polymerization:

[0409] The detailed description of the polymerization process is as follows:

[0410] Step 1: Prepolymerization and bulk homopolymerization

[0411] A 20.9L stainless steel reactor containing 0.4 barg propylene was filled with 3950g propylene. Triethylaluminum (0.80 ml of 0.62 mol / L heptane solution) was injected into the reactor through an additional 240g propylene. The solution was stirred at 20°C and 250rpm for at least 20 minutes. The catalyst was injected as described below. The required amount of solid catalyst was loaded into a 5ml stainless steel vial, and then another 5ml vial containing 4ml n-heptane was added to the top of the glove box. The vial at the top was then pressurized with 5 bar of nitrogen. The catalyst feeder system was installed on the port on the reactor cover. Immediately thereafter, 2.0 or 0.1NL of H2 (see polymerization table) was added within one minute through a mass flow controller. The valve between the two vials was opened to contact the solid catalyst with heptane under nitrogen pressure for 2 seconds, and then it was rinsed into the reactor with 340 grams of propylene. The prepolymerization was carried out at 20°C for 10 minutes. At the end of the prepolymerization step, the temperature was raised to 75°C. When only 0.1 NL of H2 was added before the catalyst, 1.9 NL of H2 was added through a mass flow controller when the internal reactor temperature reached 60° C. The reactor temperature was kept constant at 75° C. throughout the polymerization. The polymerization time was measured when the internal reactor temperature reached 2° C. below the set polymerization temperature.

[0412] Step 2: Gas-phase ethylene-propylene copolymerization

[0413] After the bulk homopolymerization step was completed, the stirrer speed was reduced to 50 rpm and the pressure was reduced to 0.4 barg by venting the monomers. Triethylaluminum (0.80 ml of a 0.62 mol / l heptane solution) was then injected into the reactor via a steel bottle with an additional 250 g of propylene. The pressure was then reduced again to 0.4 barg by venting the monomers. The stirrer speed was set to 180 rpm and the reactor temperature was set to 70°C.

[0414] The reactor pressure was then increased to 20 barg by feeding the desired C3 / C2 gas mixture (see polymerization table), the composition of which was defined by:

[0415]

[0416] Where C2 / C3 is the weight ratio of the two monomers and R is their reactivity ratio. In this experiment, the R of zirconium catalysts CE1a and CE1b are 0.44 and 0.49 respectively, and the R of hafnium catalyst IE1a is 0.38.

[0417] The temperature was kept constant by a thermostat and the pressure was kept constant by feeding a C3 / C2 gas mixture corresponding to the target polymer composition through a mass flow controller until the set time of the step was completed.

[0418] The reactor was then cooled to about 30°C and the volatile components flashed off. After purging the reactor 3 times with N2 and one vacuum / N2 cycle, the product was taken out and dried overnight in a fume hood. 100 g of the polymer was added with 0.5 wt% Irganox B225 (acetone solution) and dried overnight in a fume hood and then dried in a vacuum drying oven at 60°C for one hour.

[0419] Table 2. Aggregation example: setup, pre-aggregation, and transition to ontology steps

[0420]

[0421] Table 3. Polymerization examples: bulk, transition to gas phase, and gas phase steps

[0422]

[0423]

[0424] Table 4. Aggregation example: Results

[0425]

[0426]

[0427] Table 5. Polymer properties

[0428]

[0429]

[0430] CPE11 (Ziegler Natta heterophasic polypropylene copolymer) and CPE12 (heterophasic polypropylene copolymer prepared according to WO2013 / 007650) were also compared. Both examples were prepared in a pilot plant at Borstar with a prepolymerization reactor chain: loop; first gas phase reactor and second gas phase reactor. CPE11 used TEAL and donor. Details of the production process are shown in Table 6.

[0431] Table 6

[0432]

[0433]

[0434] Table 7 - Other properties of Examples 1 and 2.

[0435] IE1 and IE2 (or mixtures thereof), CPE11 or CPE12 were mixed with 0.15 parts of Irganox B225 and 0.05 parts of calcium stearate. The properties of the blends are provided below.

[0436] IPE1 IPE2 IPE1 (50 wt%) + IPE2 (49.8 wt%) CPE11 CPE12 Flexural modulus MPa 1387 1439 1415 1071 735 SF Wt% 8 7 14 16 G' MPa 712 706 740 573 466 Tg1 ℃ 1.2 1.2 1.2 1.2 -0.9 Tg2 ℃ -50.5 -55.7 -59.7 -51.4 -32.9 Notched impact strength / 23℃ kJ / m2 52.05 17.0 44.22 39.76 30 Notched impact strength / -20℃ kJ / m2 5.42 4,7 4.66 2.15 1.25 C2 wt% 3.46 3.06 6.22 4.23 MFR g / 10min 0.7 0.8 0.4 0.9 Tm ℃ 160.2 159.4 163 154 C2(SF) Wt% 28.35 44.77 33.86 17.04 IV(SF) dl / g 6.38 6.01 2.16 1.47

[0437] CE13 to 14 were synthesized using (rac-trans-dimethylsilanediyl[2-methyl-4-(3',5'-dimethylphenyl)-1,5,6,7-tetrahydro-s-indacene-1-yl][2-methyl-4-(3',5'-dimethylphenyl)-5-methoxy-6-tert-butylindene-1-yl]zirconium dichloride) according to the process described in WO2019 / 007655, pp 49ff.

[0438]

[0439] Preparation of MAO-silica carrier

[0440] A steel reactor equipped with a mechanical stirrer and a filter screen was flushed with nitrogen, and the reactor temperature was set to 20°C. Next, silica grade DM-L-303 from AGC Si-Tech Co was added from the feed tank, pre-calcined at 600°C (5.0kg), and then carefully pressurized and decompressed with nitrogen using a manual valve. Toluene (22kg) was then added. The mixture was stirred for 15 minutes. Next, a 30wt% MAO toluene (9.0kg) solution from Lanxess was added through the feed line at the top of the reactor within 70 minutes. The reaction mixture was then heated to 90°C and stirred for another 2 hours at 90°C. The slurry was allowed to settle and the mother liquor was filtered out. The catalyst was washed twice with toluene (22kg) at 90°C, followed by precipitation and filtration. The reactor was cooled to 60°C and the solid was washed with heptane (22.2kg). Finally, the SiO2 treated with MAO was dried at 60° for 2 hours under a nitrogen stream, and then dried for 5 hours under vacuum (-0.5 barg) under stirring. The MAO treated support was collected as a free flowing white powder and was found to contain 12.2 wt% Al.

[0441] Catalyst preparation

[0442] 30 wt% MAO in toluene (0.7 kg) was added to a steel nitrogen-sealed reactor by a burette at 20°C. Toluene (5.4 kg) was then added under stirring. MC3 (93 g) was added from a metal cylinder and then rinsed with 1 kg toluene. The mixture was stirred at 20°C for 60 minutes. Triphenylcarbonium tetrakis (pentafluorophenyl) borate (91 g) was then added from a metal cylinder and subsequently rinsed with 1 kg toluene. The mixture was stirred at room temperature for 1 hour. The resulting solution was added to the stirred cake of the MAO-silica support prepared as described above for more than 1 hour. The filter cake was allowed to stay for 12 hours and then dried at 60°C under a N2 stream for 2 hours and further dried under vacuum (-0.5 barg) for 5 hours under stirring. The dried catalyst was sampled as a pink, free-flowing powder containing 13.9% aluminum and 0.11% zirconium.

[0443] The polymerization was carried out in a 25 L mini-reactor. The detailed description of the polymerization process is shown in Table 8.

[0444] Table 8 Aggregate data

[0445]

[0446]

[0447] The polymer powder was stabilized with 1500 ppm of Irganox B225 (supplied by BASF) and 500 ppm of synthetic hydrotalcite (MAHC). CE13 is such a base polymer. CE14 is a base polymer nucleated with 2000 ppm of NA 21, commercially available from Adeka.

[0448] IE3 and IE4 were compounded with 0.15 parts of Irganox B225 and 0.05 parts of calcium stearate. The properties of the blends are provided below.

[0449] Table 9 Other properties of IE3 and IE4

[0450]

[0451]

[0452] The examples of the present invention show that heterophasic polypropylene copolymers with low SF content and low ethylene content in SF and high melting point are possible. The heterophasic polypropylene copolymers also have high IV (SF). This combination of properties produces a polymer with good stiffness, impact balance and the potential to reduce the use of the polymer in articles.

[0453] We have also demonstrated that the copolymers of the present invention have improved stiffness (low MFR, high flexural modulus) and good notched impact strength, especially at low temperatures, relative to the heterophasic polypropylene Ziegler Natta copolymer CPE11 and the metallocene heterophasic polypropylene copolymer CPE12.

[0454] In Table 9, we demonstrate that the combination of a high Tm matrix (shown by the high overall Tm) with a very high Mw rubber (shown by the high IV of the SF) provides an excellent stiffness / impact balance, especially at low temperatures.

Claims

1. A method for preparing a heterophasic polypropylene copolymer, comprising: (I) polymerizing propylene and optionally ethylene and / or 1-butene in the presence of a catalyst to form: a1) a crystalline fraction comprising a propylene homopolymer or a propylene copolymer with ethylene and / or 1-butene with 0 to 3 wt.% of comonomer as matrix component; and (II) subsequently polymerizing additional propylene and ethylene and optionally 1-butene in the presence of the matrix component of step (I) to form: a2) a soluble fraction of a propylene-ethylene copolymer or a propylene-ethylene-1-butene copolymer having a comonomer content of 12 to 45% by weight; The crystalline part accounts for 55.0 to 95.0 wt. % of the heterophasic propylene-ethylene copolymer or the heterophasic propylene-ethylene-1-butene copolymer, and the soluble part accounts for 5.0 to 45.0 wt. %, wherein the amount of the crystalline fraction and the amount of the soluble fraction are determined in 1,2,4-trichlorobenzene at 40°C; and wherein the soluble fraction of the heterophasic propylene-ethylene copolymer or the heterophasic propylene-ethylene-1-butene copolymer has an intrinsic viscosity IV in decalin at 135°C of 2.5 to 11 dl / g; And the catalyst comprises (i) a metallocene complex represented by formula (I): Each X is a σ-ligand; In the R2Si- group, at least one R is methyl or ethyl and the other R is selected from methyl, ethyl, n-propyl, isopropyl, n-butyl or isobutyl, pentyl, hexyl, cyclohexyl and phenyl; Each R 1 are independently the same or different and are CH2-R 7 Group, where R 7 Is H or straight or branched chain C 1-6 Alkyl, C 3-8 Cycloalkyl or C 6-10 Aryl; Each R 2 are independently -CH=, -CY=, -CH2-, -CHY- or -CY2- groups, wherein Y is C 1-6 Hydrocarbyl wherein n is 2-6; Each R 3 and R 4 are independently the same or different and are hydrogen, straight or branched chain C 1-6 Alkyl, C 7-20 Aralkyl, C 7-20 Alkyl aryl, C 6-20 Aryl or -OY group, where Y is C 1-6 Hydrocarbon; R 5 Straight or branched chain C 1-6 Alkyl, C 7-20 Aralkyl, C 7-20 Alkyl aryl or C 6-20 aryl; and R 6 C(R 8 )3 groups, each R 8 are independently linear or branched C 1-6 alkyl; (A) wherein each phenyl group has at least one R 3 and at least one R 4 is not hydrogen, and wherein for each phenyl group at least one R 3 and at least one R 4 is hydrogen; or (B) One of the R 3 is an -OY group, where Y is C 1-6 Hydrocarbon, at the 4-position of each phenyl group, two additional R 3 The group is tert-butyl; and / or (C) One of the R 4 is an -OY group, where Y is C 1-6 Hydrocarbon, at the 4th position of the benzene ring, the other two R 4 The group is tert-butyl; (ii) A co-catalyst comprising a Group 13 metal compound.

2. The method for preparing a heterophasic polypropylene copolymer according to claim 1, comprising: (I) polymerizing propylene and optionally ethylene and / or 1-butene in the presence of a catalyst to form: a1) a crystalline fraction comprising a propylene homopolymer or a propylene copolymer wherein ethylene and / or 1-butene with 0 to 2 wt.% of comonomers as the matrix component; and (II) subsequently polymerizing additional propylene and ethylene and optionally 1-butene in the presence of the matrix component of step (I) to form: a2) a soluble fraction of a propylene-ethylene copolymer or a propylene-ethylene-1-butene copolymer having a comonomer content of 12 to 45% by weight; The crystalline part accounts for 75.0 to 95.0 wt. % of the heterophasic propylene-ethylene copolymer or the heterophasic propylene-ethylene-1-butene copolymer, and the soluble part accounts for 5.0 to 25.0 wt. %, wherein the amount of the crystalline fraction and the amount of the soluble fraction are determined in 1,2,4-trichlorobenzene at 40°C; and wherein the soluble fraction of the heterophasic propylene-ethylene copolymer or the heterophasic propylene-ethylene-1-butene copolymer has an intrinsic viscosity IV in decalin at 135°C of 2.5 to 10 dl / g; And the catalyst comprises (i) a metallocene complex represented by formula (I): Each X is a σ-ligand; In the R2Si- group, at least one R is methyl or ethyl and the other R is selected from methyl, ethyl, n-propyl, isopropyl, n-butyl or isobutyl, pentyl, hexyl, cyclohexyl and phenyl; Each R 1 are independently the same or different and are CH2-R 7 Group, where R 7 Is H or straight or branched chain C 1-6 Alkyl, C 3-8 Cycloalkyl or C 6-10 Aryl; Each R 2 are independently -CH=, -CY=, -CH2-, -CHY- or -CY2- groups, wherein Y is C 1-6 Hydrocarbyl wherein n is 2-6; Each R 3 and R 4 are independently the same or different and are hydrogen, straight or branched chain C 1-6 Alkyl, C 7-20 Aralkyl, C 7-20 Alkyl aryl, C 6-20 Aryl or -OY group, where Y is C 1-6 Hydrocarbon; R 5 Straight or branched chain C 1-6 Alkyl, C 7-20 Aralkyl, C 7-20 Alkyl aryl or C 6-20 aryl; and R 6 C(R 8 )3 groups, each R 8 are independently linear or branched C 1-6 alkyl; (A) wherein each phenyl group has at least one R 3 and at least one R 4 is not hydrogen, and wherein for each phenyl group at least one R 3 and at least one R 4 is hydrogen; or (B) One of the R 3 is an -OY group, where Y is C 1-6 Hydrocarbon, at the 4-position of each phenyl group, two additional R 3 The group is tert-butyl; and / or (C) One of the R 4 is an -OY group, where Y is C 1-6 Hydrocarbon, at the 4th position of the benzene ring, the other two R 4 The group is tert-butyl; (ii) A co-catalyst comprising a Group 13 metal compound.

3. The process for preparing a heterophasic polypropylene copolymer according to claim 1 or 2, wherein in step (II), additional propylene and ethylene and optionally 1-butene are polymerized in the gas phase.

4. The method for preparing a heterophasic polypropylene copolymer according to claim 1 or 2, wherein the co-catalyst of the Group 13 metal compound is aluminum or boron.

Citation Information

Patent Citations

  • Heterophasic polypropylene with high impact properties

    EP2072546A1

  • Phthalocyanine dyes, their preparation and use

    EP2072584A1

  • Heterophasic polypropylene with excellent creep performance

    EP2368937A1

  • Heterophasic copolymer

    EP2824142A1

  • Process

    EP2829558A1